Fireproof plate and preparation method thereof

CN122899259APending Publication Date: 2026-10-13JIANGSU JICUI SURFACE ENGINEERING TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611222130.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]同时,本发明提供一种防火板的制备方法,该法获得的微胶囊壁材 200℃以上破损后,芯材释放并与基材层、防火表层形成 “三级反应链”,既放大产气量,又通过层间结构锁定气体、强化灭火效果,解决传统微胶囊 “产气易散、灭火单一” 的缺陷

Benefits of technology

一、本发明的核心协同体系设计:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899259A_ABST
    Figure CN122899259A_ABST
Patent Text Reader

Abstract

The application discloses a fireproof plate and a preparation method thereof, and belongs to the technical field of fireproof plates. The fireproof plate comprises, from inside to outside, a substrate layer, a microcapsule composite layer and a fireproof surface layer, wherein the thickness of the substrate layer is 8-15 mm, the thickness of the microcapsule composite layer is 2-5 mm, and the thickness of the fireproof surface layer is 2-5 mm. The fireproof plate has a bending strength of greater than or equal to 18 MPa, a compressive strength of greater than or equal to 25 MPa, and an interlayer peeling strength of greater than or equal to 1.2 N / mm; the gas production rate is greater than or equal to 1.5 L / (g.min) within 30 s after triggering at 200 DEG C, the oxygen concentration is reduced to below 12%, and there is no afterburning after extinguishing. After the microcapsule wall material is damaged at more than 200 DEG C, the core material is released and forms a 'three-level reaction chain' with the substrate layer and the fireproof surface layer, thereby amplifying the gas production, locking the gas through the interlayer structure and strengthening the extinguishing effect, and solving the defects of traditional microcapsules, i.e., easy dispersion of gas production and single extinguishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a fireproof board and its preparation method, belonging to the field of fireproof board technology. Background Technology

[0002] With the rapid development of industrialized construction and the new energy industry, fireproof boards, as key safety protection materials, have been widely used in many core scenarios such as high-rise building partitions, new energy battery compartments, medical facilities, and underground spaces. The market's requirements for their fire resistance performance have upgraded from the traditional "passive isolation" to "active fire extinguishing, multiple protections, safety and environmental protection, and precise adaptation." However, existing fireproof board technology still faces many bottlenecks that are difficult to overcome, and cannot meet the comprehensive needs of diversified scenarios. Traditional Class A fireproof boards mostly use a single inorganic mineral as the core material, relying solely on physical isolation to achieve passive fire protection, lacking the ability to actively suppress fire. Even if some products embed microcapsules, they mostly adopt a simple mechanism of "physical rupture to release the core material." The core material is mostly halon or inert gas, which not only has a limited gas production (1kg of microcapsule usually produces less than 200L of gas), but the gas also diffuses quickly, making it difficult to form an effective fire extinguishing concentration within the protected space, and it is even less effective against fire sources in hidden gaps. Meanwhile, existing products have limited functionality, focusing solely on fire isolation and lacking synergistic protective effects such as cooling, resistance to reignition, and sealing. During a fire, they cannot reduce the high temperatures, easily leading to panel collapse. After fire extinguishing, the lack of subsequent flame-retardant protection results in a reignition rate exceeding 35%. Furthermore, the high-temperature decomposition of some core materials can produce toxic and harmful gases, making them unsuitable for occupied areas. In addition, the interlayer structure design of existing products lacks synergy; the microcapsules do not interact with other components of the panel, preventing the amplification of gas production through interlayer action. Their fixed thickness specifications make it difficult to adapt to the differentiated needs of various scenarios, such as new energy battery compartments (requiring long-term fire suppression and reignition resistance) and ordinary building partitions (requiring lightweight and low cost). Mechanical and fire resistance performance are also often difficult to balance; prioritizing fire resistance results in insufficient mechanical strength, while pursuing lightweight design leads to reduced fire resistance.

[0003] Against this backdrop, existing fireproof board technology still has many unresolved issues and struggles to meet the comprehensive requirements of "active fire suppression, multiple protections, scenario adaptability, and safety and environmental protection." Therefore, there is an urgent need to develop a fireproof board to address these problems. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a fireproof board with a bending strength ≥18MPa, compressive strength ≥25MPa, and interlayer peel strength ≥1.2N / mm; a gas generation rate ≥1.5L / (g•min) within 30s after being triggered at 200℃, an oxygen concentration reduced to below 12%, and no reignition after extinguishing the fire.

[0005] Meanwhile, this invention provides a method for preparing a fireproof board. After the microcapsule wall material obtained by this method is broken at temperatures above 200°C, the core material is released and forms a "three-level reaction chain" with the substrate layer and the fireproof surface layer. This not only amplifies the gas production, but also locks the gas through the interlayer structure and enhances the fire extinguishing effect, thus solving the defects of traditional microcapsules that "produce gas easily and extinguish fires in a single way".

[0006] Meanwhile, this invention provides an application of fireproof board in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A fireproof board comprises, from the inside out, a substrate layer, a microcapsule composite layer, and a fireproof surface layer.

[0008] The substrate layer comprises the following raw materials: 30-40 parts by weight of modified magnesium hydroxide, 55-65 parts by weight of modified calcium carbonate, 8-12 parts by weight of pre-thickened styrene-acrylic emulsion, and 5-8 parts by weight of talc.

[0009] The preparation method of modified magnesium hydroxide is as follows: take magnesium hydroxide (purity ≥98%, initial particle size 10-50μm) for surface activation modification, mix magnesium hydroxide and stearic acid at a mass ratio of 100:2-100:4, add ethanol solution (solid-liquid ratio 1:10-1:15), stir at 70-80℃ for 2-3h, centrifuge (speed 3000-4000r / min, 15-20min), the precipitate is vacuum dried at 80-100℃ for 4-6h, ground through a 300-400 mesh sieve, control the particle size of modified magnesium hydroxide to 10-20μm, improve the compatibility and dispersion uniformity with adhesives, and obtain modified magnesium hydroxide.

[0010] The preparation method of modified calcium carbonate is as follows: Take calcium carbonate (heavy, whiteness ≥93%), mix calcium carbonate and deionized water at a mass ratio of 1:3-1:5, add sodium hexametaphosphate dispersant equivalent to 0.5-1.0wt% of calcium carbonate, grind at a speed of 2000-3000r / min for 60-90min, spray dry (inlet air 180-200℃, outlet air 80-90℃), collect powder with a particle size of 5-15μm, dry at 60-70℃ for 3-4h for later use, and obtain modified calcium carbonate.

[0011] The preparation method of pre-thickened styrene-acrylic emulsion is as follows: Take an aqueous styrene-acrylic emulsion (solid content 40%-50%), add 0.3-0.5 wt% of hydroxyethyl cellulose to the aqueous styrene-acrylic emulsion, stir at 50-60℃ for 30-40 min, adjust the viscosity to 1500-2000 mPa•s (25℃) to avoid sagging during coating, and obtain the pre-thickened styrene-acrylic emulsion.

[0012] The microcapsule composite layer comprises the following raw materials: 65-72 parts by weight of inorganic filler, 18-25 parts by weight of microcapsule suspension (dry surface-modified microcapsules), 7-10 parts by weight of water-based styrene-acrylic emulsion, and 1-2 parts by weight of film-forming aid.

[0013] Inorganic fillers include modified talc.

[0014] Film-forming aids include ethylene glycol butyl ether.

[0015] The preparation method of modified talc is as follows: Take (talc powder, particle size 5-10μm) and modify it with silane. Mix talc powder with KH-550 silane coupling agent at a mass ratio of 100:1-100:2, add ethanol-water mixed solution (the volume ratio of ethanol to water in the ethanol-water mixed solution is 6:4), solid-liquid ratio is 1:11-1:18, stir at 60-70℃ for 2-3h, remove the solvent by vacuum distillation, dry at 70-80℃ for 4-5h to improve the binding force with microcapsules and adhesives, and the modified talc powder is obtained.

[0016] The preparation method of the microcapsule suspension is as follows: surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:5-1:8, and 0.2-0.3wt% (equivalent to 0.2-0.3wt% of the total mass of microcapsules and deionized water) of polyethylene glycol (PEG-4000) is added. The mixture is then ultrasonically dispersed (power 300-400W, time 10-15min) to form a stable suspension, thus avoiding the aggregation of microcapsules in the composite layer, and the microcapsule suspension is obtained.

[0017] The preparation method of microcapsules is as follows: The microcapsules of this invention are prepared using a four-stage process: core material pretreatment, wall material modification, stepwise encapsulation, and post-crosslinking reinforcement, as detailed below: S1. Raw material pretreatment S11. Core Material Pretreatment S111. Aminosulfonic acid (purity ≥99.5%): Processed by air jet milling, with an inlet pressure of 0.6-0.8 MPa and a milling time of 20-30 min. The powder with a particle size of 5-10 μm is collected by passing it through a 400-600 mesh standard sieve and placed in a vacuum drying oven at 60-80℃ for 4-6 h to remove surface adsorbed water and prevent subsequent agglomeration.

[0018] S112. Ammonium bicarbonate (purity ≥99.0%): dried under low temperature vacuum at 40-50℃, vacuum degree -0.08~-0.09MPa, for 6-8 hours. After crushing, it is passed through a 300-500 mesh sieve to control the particle size to 10-20μm, avoiding premature decomposition at high temperature.

[0019] S113. Nano-montmorillonite (particle size 5-10nm): Mix nano-montmorillonite with hexadecyltrimethylammonium bromide at a mass ratio of 10:1-10:2, add deionized water (solid-liquid ratio 1:20-1:30, unit is g / L), stir at 80-90℃ for 2-3h, centrifuge (speed 3000-4000r / min, time 15-20min), dry the precipitate under vacuum at 60-70℃ for 8-12h, grind through a 300-500 mesh sieve to improve compatibility with organic core materials.

[0020] S12. Pretreatment of wall material raw materials S121. Ammonium polyphosphate (APP, degree of polymerization n=1000-1500, phosphorus content ≥30%): Add APP to an ethanol-water mixture (ethanol to water volume ratio 7:3), solid-liquid ratio 1:15-1:25, add 3-5wt% (3-5wt% of the total mass of APP and ethanol-water mixture) of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560), stir at 60-70℃ for 3-4h, remove solvent by vacuum distillation (temperature 50-60℃, vacuum degree -0.07~-0.08MPa), and vacuum dry at 50-60℃ for 4-6h to obtain modified APP, which improves the reactivity of APP with MF resin.

[0021] S122. Preparation of melamine-formaldehyde resin (MF) prepolymer: A formaldehyde solution (37% by mass) is placed in a reactor at a formaldehyde to melamine molar ratio of 2.5:1-3.0:1. The pH is adjusted to 8.5-9.0, melamine is added, and the mixture is stirred at 40-50℃ for 30-40 minutes until completely dissolved. The temperature is then raised to 70-80℃ and reacted for 60-90 minutes to obtain an MF prepolymer with a solid content of 30%-40%. The prepolymer is cooled to room temperature and kept at 60%-70% hydroxymethylation.

[0022] S2. Core Material Preparation S21. Primary mixing: Place the pretreated aminosulfonic acid and ammonium bicarbonate in a mass ratio of 3:5-3:6 in a double planetary mixer, add 2-3wt% (accounting for 2-3wt% of the total mass of the core material) of polyethylene glycol (PEG-6000) as a dispersant, and stir at low speed (300-500r / min) for 20-30min to initially mix evenly.

[0023] S22. Secondary dispersion: Add pretreated nano-montmorillonite (accounting for 15%-20% of the total mass of the core material), heat to 70-80℃, stir at high speed (1500-2000r / min) for 40-60min, and at the same time purge nitrogen (flow rate 0.5-1.0L / min) for protection to avoid oxidative decomposition of ammonium bicarbonate.

[0024] S23. Granulation and molding: Add the mixed slurry to a spray dryer with an inlet air temperature of 160-180℃, an outlet air temperature of 70-90℃, an atomization pressure of 0.3-0.5MPa, and a feed rate of 20-30mL / min to obtain initial core material particles.

[0025] S24. Grading and screening: The initial core material particles after spray drying are screened by an air classifier at a grading pressure of 0.4-0.6MPa. Core material particles with a particle size of 30-50μm are collected, and the particle size distribution range is controlled within 1.2-1.5 to ensure the uniformity of subsequent coating.

[0026] S25. Core material stabilization treatment: The screened core material is placed in a constant temperature and humidity chamber and matured for 24-48 hours at a temperature of 30-40℃ and a relative humidity of 40%-50% to eliminate internal stress and improve the storage stability of the core material.

[0027] S3. Wall material preparation S31. Preparation of basic emulsion: Mix modified APP and MF prepolymer at a mass ratio of 4:6-5:5, add ethanol as solvent, solid-liquid ratio of 1:8-1:12, adjust pH to 7.5-8.5, stir at 50-60℃ for 60-90 min at a speed of 800-1200 r / min to form a uniform wall material basic emulsion.

[0028] S32. Crosslinking agent adjustment: Add 5%-8% of adipic acid dihydrazide by mass of MF prepolymer as a crosslinking agent, continue stirring for 30-40 minutes, control the crosslinking degree of the wall material emulsion and the precursor content to 25%-35%, and ensure the density of the wall material after subsequent coating.

[0029] S33. Emulsion Stabilization: Add 0.5-1.0 wt% of polyvinyl alcohol (PVA-1788) as a stabilizer, ultrasonically disperse (power 300-500W, time 15-20min) to eliminate emulsion bubbles, let stand for 20-30min, take the upper homogeneous emulsion for later use, and control the emulsion solid content at room temperature to 25%-30% and the viscosity to 500-800mPa•s.

[0030] S4. Coating reaction S41. Pre-coating stage: Add the stabilized wall material emulsion to the reactor, introduce nitrogen gas (flow rate 1.0-1.5L / min), add the core material particles after classification and screening, with a core material particle to wall material emulsion mass ratio of 1:3-1:5, adjust the pH to 8.0-8.5, raise the temperature to 45-55℃, stir at low speed (200-300r / min) for 30-40min, and simultaneously use ultrasonic-assisted dispersion (power 200-300W, intermittent ultrasonic: work for 5min, pause for 3min, cycle 3-5 times) to make the core material particles uniformly dispersed in the wall material emulsion, forming a primary coating system.

[0031] S42. In-situ polymerization stage: The temperature is increased in stages. In the first stage, the temperature is increased to 60-65℃ at a rate of 1-2℃ / min, and the stirring speed is increased to 500-700r / min. The reaction time is 60-90min to promote the initial polymerization of the wall material on the surface of the core material. In the second stage, the temperature is increased to 70-75℃, and the stirring speed is increased to 800-1000r / min. The reaction time is 90-120min to form a dense three-dimensional network structure of the wall material. During the reaction, the coating thickness is sampled and tested every 30min to control the thickness of the primary wall material to 20-30μm.

[0032] S43. Post-crosslinking stage: Add melamine equivalent to 3%-5% of the total mass of the wall material as a crosslinking agent, adjust the pH to 7.0-7.5, keep it at 75-80℃ for 60-80 minutes to strengthen the crosslinking structure of the wall material and improve its thermal stability and sealing performance.

[0033] S5. Post-processing technology S51. Washing and purification: Centrifuge the encapsulated microcapsule suspension (4000-6000 r / min, 20-30 min), remove the supernatant, wash 3-5 times with an ethanol-water mixture (volume ratio 1:1) to remove unreacted monomers and free wall material; then wash 2-3 times with deionized water to remove residual ethanol and ensure that there are no impurities on the surface of the microcapsules.

[0034] S52. Freeze-drying: Place the washed microcapsules in a freeze dryer, pre-freeze at -40~-50℃ for 2-4 hours, then adjust the vacuum degree to 10-20Pa, raise the temperature to -10~0℃, and dry for 24-36 hours to avoid the core material decomposition or wall material deformation caused by high temperature, and obtain a loose and dry microcapsule intermediate.

[0035] S53. Surface-modified microcapsules: Add the microcapsule intermediate to an ethanol solution with a solid-liquid ratio of 1:10-1:15, add 1-2 wt% KH-550 silane coupling agent equivalent to the mass of the microcapsule intermediate, stir at 50-60℃ for 60-90 min, centrifuge (3000-4000 r / min, 15-20 min), and vacuum dry at 50-60℃ for 4-6 h to improve the compatibility and bonding force between the microcapsules and the various layers of the fireproof board.

[0036] S54. Grading and Quality Control: The surface-modified microcapsules are screened by a vibrating screen with a pore size of 80-120μm to remove oversized or undersized particles and ensure uniform microcapsule size. Random samples are taken to test the encapsulation rate (≥85%), wall thickness (20-40μm), and thermal decomposition temperature (200-230℃). Unqualified products are returned to the washing process for reprocessing.

[0037] S55. Stabilization storage: Place qualified microcapsules in a vacuum packaging container, add desiccant (montmorillonite desiccant, 5%-8% of the mass of the microcapsules), and store in an environment with a temperature of 20-30℃ and a relative humidity of ≤60%. Shelf life is ≥12 months.

[0038] Specifically, the surface-modified microcapsules include a core material and a wall material; the surface of the wall material is modified with KH-550 silane coupling agent; The core material comprises the following raw materials: aminosulfonic acid, ammonium bicarbonate, and modified nano-montmorillonite; the mass ratio of aminosulfonic acid to ammonium bicarbonate is 3:5-3:6, and the modified nano-montmorillonite accounts for 15%-20% of the total mass of the core material; The wall material includes the following raw materials: modified ammonium polyphosphate, melamine-formaldehyde resin prepolymer, crosslinking agent and stabilizer; the mass ratio of modified ammonium polyphosphate and melamine-formaldehyde resin prepolymer is 4:6-5:5, the weight of crosslinking agent is 5%-8% of the weight of melamine-formaldehyde resin prepolymer, and the weight of stabilizer is 0.5-1.0 wt% of the weight of melamine-formaldehyde resin prepolymer.

[0039] The fireproof surface layer comprises the following raw materials: 15-20 parts by weight of intercalated modified expandable graphite, 75-82 parts by weight of modified epoxy resin, 2-4 parts by weight of modified nano silica, and 3-5 parts by weight of coupling agent (including silane coupling agent KH550).

[0040] The preparation method of intercalated modified expandable graphite is as follows: Take expandable graphite (expansion ratio ≥30 times, particle size 20-50μm, model: SGL carbon, manufacturer: SGL Graphite, Germany), mix expandable graphite and phosphoric acid at a mass ratio of 10:1-10:3, stir at 60-70℃ for 60-90min, wash with deionized water until pH=6-7, centrifuge (speed 3000-5000r / min, 10-15min), vacuum dry at 80-90℃ for 6-8h to improve the expansion rate and compatibility with resin, and the intercalated modified expandable graphite is obtained.

[0041] The modified epoxy resin is prepared as follows: Take epoxy resin (E-44), dilute and modify it, add acetone (epoxy resin to acetone volume ratio 1:0.3-1:0.5), stir at 40-50℃ for 30-40 min, add 2-3 wt% (equivalent to 2-3 wt% of the total mass of epoxy resin and acetone) of triethylenetetramine curing agent, stir for 15-20 min, and adjust the viscosity to 800-1200 mPa•s (25℃) to obtain the modified epoxy resin.

[0042] The preparation method of modified nano silica is as follows: Take nano silica (particle size 10-20nm), perform hydrophobic modification, mix nano silica with methyltriethoxysilane at a mass ratio of 100:3-100:5, add toluene solution (solid-liquid ratio 1:20-1:30), reflux and stir at 80-90℃ for 3-4h, filter, and dry at 90-100℃ for 5-6h to improve the surface wear resistance and self-cleaning performance, thus obtaining modified nano silica.

[0043] A method for preparing a fireproof board according to the present invention includes the following steps: The fireproof board of this invention adopts a five-stage preparation process: layered preparation, interface modification, stepwise composite, gradient curing, and post-treatment strengthening, as detailed below: S1. Pretreatment of raw materials for each layer of fireproof board S11. Pretreatment of substrate material S111. Magnesium hydroxide (purity ≥98%, initial particle size 10-50μm): Surface activation modification is performed by mixing magnesium hydroxide and stearic acid at a mass ratio of 100:2-100:4, adding ethanol solution (solid-liquid ratio 1:10-1:15), stirring at 70-80℃ for 2-3 hours, centrifuging (3000-4000r / min, 15-20min), drying the precipitate under vacuum at 80-100℃ for 4-6 hours, grinding through a 300-400 mesh sieve, controlling the modified particle size to 10-20μm, improving compatibility and dispersion uniformity with adhesives.

[0044] S112. Calcium carbonate (heavy, whiteness ≥93%): Wet ultrafine grinding is performed by mixing calcium carbonate and deionized water at a mass ratio of 1:3-1:5, adding sodium hexametaphosphate dispersant equivalent to 0.5-1.0wt% of calcium carbonate, grinding speed 2000-3000r / min, grinding time 60-90min, spray drying (inlet air 180-200℃, outlet air 80-90℃), collecting powder with a particle size of 5-15μm, and drying at 60-70℃ for 3-4h for later use.

[0045] S113. Aqueous styrene-acrylic emulsion (solid content 40%-50%): Pre-thickening treatment, add 0.3-0.5 wt% of hydroxyethyl cellulose to the aqueous styrene-acrylic emulsion, stir at 50-60℃ for 30-40 min, adjust the viscosity to 1500-2000 mPa•s (25℃) to avoid sagging during coating.

[0046] S12. Pretreatment of raw materials for microcapsule composite layers S121. Inorganic filler (talc powder, particle size 5-10μm): Silane modification is performed by mixing talc powder with KH-550 silane coupling agent at a mass ratio of 100:1-100:2, adding an ethanol-water mixed solution (the volume ratio of ethanol to water in the ethanol-water mixed solution is 6:4), with a solid-liquid ratio of 1:11-1:18, stirring at 60-70℃ for 2-3 hours, removing the solvent by vacuum distillation, and drying at 70-80℃ for 4-5 hours to improve the binding force with microcapsules and adhesives.

[0047] S122. Pretreated microcapsules: Co-dispersion treatment, the surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:5-1:8, and 0.2-0.3wt% (equivalent to 0.2-0.3wt% of the total mass of microcapsules and deionized water) of polyethylene glycol (PEG-4000) is added. The mixture is then ultrasonically dispersed (power 300-400W, time 10-15min) to form a stable suspension and avoid microcapsule aggregation in the composite layer.

[0048] S13. Pretreatment of fire-resistant surface material S131. Expandable graphite (expansion ratio ≥30 times, particle size 20-50μm, model: SGL carbon, manufacturer: SGL Graphite, Germany): Mix expandable graphite with phosphoric acid at a mass ratio of 10:1-10:3, stir at 60-70℃ for 60-90 min, wash with deionized water until pH=6-7, centrifuge (3000-5000 r / min, 10-15 min), and vacuum dry at 80-90℃ for 6-8 h to improve the expansion rate and compatibility with resin.

[0049] S132. Epoxy resin (E-44): Dilute and modify, add acetone (epoxy resin to acetone volume ratio 1:0.3-1:0.5), stir at 40-50℃ for 30-40 min, add 2-3 wt% (equivalent to 2-3 wt% of the total mass of epoxy resin and acetone) of triethylenetetramine curing agent, stir for 15-20 min, and adjust the viscosity to 800-1200 mPa•s (25℃).

[0050] S133. Nano silica (particle size 10-20nm): Hydrophobic modification, nano silica is mixed with methyltriethoxysilane at a mass ratio of 100:3-100:5, toluene solution is added (solid-liquid ratio 1:20-1:30), refluxed and stirred at 80-90℃ for 3-4h, filtered and dried at 90-100℃ for 5-6h to improve the surface wear resistance and self-cleaning performance.

[0051] S2. Individual preparation process for each layer S21. Substrate layer preparation S211. Primary mixing: Place 30-40 parts of modified magnesium hydroxide, 55-65 parts of modified calcium carbonate, 8-12 parts of pre-thickened styrene-acrylic emulsion, and 5-8 parts of talc into a high-speed kneader and stir at low speed (300-500 r / min) for 20-30 minutes to initially mix evenly.

[0052] S212. Secondary kneading: Heat to 60-70℃, stir at high speed (1000-1500r / min) for 40-60min, and simultaneously introduce nitrogen (flow rate 0.3-0.5L / min) to remove air bubbles generated during the mixing process and obtain a uniform substrate slurry.

[0053] S213. Roll forming: The slurry is fed into a two-roll mill with a roll temperature of 70-80℃, a roll speed of 20-30 r / min, and a rolling gap of 8-15 mm. After 3-5 rolling passes, the thickness of the substrate layer is controlled to be 8-15 mm to ensure a dense structure (porosity of 15%-20%).

[0054] S214. Pre-curing: Place the rolled substrate layer in a constant temperature oven and pre-cur it at 80-90℃ for 2-3 hours to remove some moisture and volatile components, improve the strength of the substrate layer, and avoid deformation during subsequent lamination.

[0055] S22. Preparation of microcapsule composite layer S221. Mixing and Dispersion: Place 65-72 parts of modified talc powder, microcapsule suspension (18-25 parts of surface-modified microcapsules after drying), 7-10 parts of aqueous styrene-acrylic emulsion, and 1-2 parts of film-forming aid (ethylene glycol butyl ether) into a planetary mixer. First, stir at low speed (500-800 rpm) for 30-40 minutes, then stir at high speed (1500-2000 rpm) for 60-90 minutes. Simultaneously, use ultrasonic-assisted dispersion (power 400-500W, intermittent: work for 10 minutes, pause for 5 minutes, cycle 3-4 times) to ensure uniform dispersion of microcapsules (distribution density 50-80 particles / mm²). 2 ).

[0056] S222. Interface treatment: Coat the surface of the pre-cured substrate layer with a layer of coupling agent dilution (KH-550 to ethanol volume ratio 1:10), coating amount 5-8 g / m². 2 Place at room temperature for 30-60 minutes to activate the substrate surface and improve the adhesion to the microcapsule composite layer (peel strength ≥1.5N / mm).

[0057] S223. Slit Extrusion Coating: The microcapsule composite layer slurry is coated onto the surface of the substrate layer using a slit extrusion coating machine. The coating temperature is 50-60℃, the coating speed is 0.5-1.0m / min, and the coating thickness is 2-5mm. The thickness deviation is controlled within ±0.1mm by real-time monitoring with a laser thickness gauge.

[0058] S224. Semi-curing: The coated board is placed in a constant temperature and humidity chamber at a temperature of 60-70℃ and a relative humidity of 50%-60% for 1-2 hours to allow the composite layer to initially form and prevent the slurry from penetrating during subsequent surface coating.

[0059] The porosity of the microcapsule composite layer obtained above is 25%-30%.

[0060] S23 fire-resistant surface preparation S231. Preparation of surface slurry: Place 15-20 parts of intercalated modified expandable graphite, 75-82 parts of modified epoxy resin, 2-4 parts of modified nano silica, and 3-5 parts of coupling agent into a high-speed disperser, stir at 60-70℃ for 60-90 min at a speed of 1200-1800 r / min to form a uniform surface slurry (solid content 60%-70%).

[0061] S232. Composite layer interface activation: Plasma treatment is performed on the surface of the semi-cured microcapsule composite layer. The plasma power is 100-150W, the treatment time is 3-5min, and the treatment distance is 5-10mm to improve the bonding force between the surface layer and the composite layer (peel strength ≥1.2N / mm).

[0062] S233. Doctor blade coating: The surface slurry is coated onto the surface of the microcapsule composite layer using a comma doctor blade coating machine. The coating angle is 30-45°, the coating speed is 0.3-0.8m / min, and the coating thickness is 2-5mm. After coating, the surface is smoothed a second time with a scraper roller to ensure the surface smoothness (surface roughness Ra≤1.0μm).

[0063] S234. Pre-drying: Place the coated board in a hot air circulating oven and pre-dry at 70-80℃ for 2-3 hours to remove solvent and moisture, and avoid the formation of bubbles or pinholes during curing.

[0064] S3. Interlayer lamination and gradient curing process S31. Layer positioning: Place the pre-dried board on the hot press workbench and fix it with positioning pins to ensure that each layer is aligned (edge ​​deviation ≤ 0.5mm) to avoid misalignment between layers affecting the synergistic effect.

[0065] S32. Stepwise hot pressing curing S321. First stage (preheating and pressurization): Heat to 100-120℃ at a rate of 2-3℃ / min, apply pressure of 3-5MPa, and maintain the temperature and pressure for 60-90min to promote the initial cross-linking of each layer of adhesive and enhance the interlayer bonding.

[0066] S322. Second stage (heat curing): Continue to heat to 150-180℃ at a rate of 1-2℃ / min, increase the pressure to 6-8MPa, and hold at the temperature and pressure for 120-180min to ensure that each layer is completely cured, while ensuring that the microcapsule wall material is not damaged (the hot pressing temperature is 20-30℃ lower than the microcapsule decomposition temperature).

[0067] S323. Third stage (cooling and depressurization): Cool down to 80-100℃ at a rate of 1-2℃ / min, reduce the pressure to 2-3MPa, maintain the temperature and pressure for 30-60min to eliminate internal stress; then let it cool naturally to room temperature, depressurize and remove the board to avoid cracking of the board due to excessive cooling.

[0068] S324. Post-curing treatment: Place the hot-pressed board in a constant temperature oven and cure at 120-140℃ for 4-6 hours to further improve the cross-linking degree of each layer and the overall mechanical properties, so that the fireproof board has a bending strength ≥18MPa and a compressive strength ≥25MPa.

[0069] S4. Post-processing and quality control technology S41. Cutting and finishing: The board is cut to length using a CNC cutting machine at a speed of 1-2m / min and a cutting accuracy of ±0.2mm. Edge burrs and irregular parts are removed to ensure that the board size meets the design requirements.

[0070] S42. Surface polishing: Polish the surface with 180-240 grit sandpaper at a speed of 3-5 m / min and a pressure of 0.1-0.3 MPa to make the surface smooth and flat, while removing residual impurities.

[0071] S43. Aging treatment: Place the sanded board in an aging test chamber at a temperature of 70℃ and a relative humidity of 90% for 72-120 hours.

[0072] S44. Performance testing: Conduct appearance inspection, dimensional inspection, mechanical testing, and fire extinguishing performance testing on the product.

[0073] Appearance inspection: The surface is free of cracks, bubbles, and missing materials, and the color is uniform; Dimensional inspection: thickness deviation ±0.3mm, length / width deviation ±0.5mm; Mechanical testing: flexural strength ≥18MPa, compressive strength ≥25MPa, interlaminar peel strength ≥1.2N / mm; Fire extinguishing performance test: After being triggered at 200℃, the gas production rate is ≥1.5L / (g•min) within 30 seconds, the oxygen concentration drops to below 12%, and there is no reignition after extinguishing the fire.

[0074] S45. Packaging and Storage: Qualified boards are packaged with waterproof film and pearl cotton to avoid damage during transportation; they are stored in a warehouse with a temperature of 20-30℃ and relative humidity of ≤60%, away from fire sources and high-temperature environments, with a storage period of ≥12 months.

[0075] The fireproof board of the present invention comprises, from the inside out, a substrate layer, a microcapsule composite layer and a fireproof surface layer. The substrate layer has a thickness of 8-15mm, the microcapsule composite layer has a thickness of 2-5mm, and the fireproof surface layer has a thickness of 2-5mm. The thickness deviation of each layer is ≤±0.1mm, and the total thickness deviation is ≤±0.3mm.

[0076] The thickness of each layer can be finely adjusted within a certain range (for example, fireproof boards for new energy battery compartments can use a base layer of 12-15mm + composite layer of 3-5mm + surface layer of 3-5mm to enhance fire extinguishing durability; fireproof boards for ordinary building partitions can use a base layer of 8-10mm + composite layer of 2-3mm + surface layer of 2-3mm to take into account lightweight).

[0077] The fireproof board of the present invention has pre-set micron-level pores in each layer, with a porosity of 15%-20% in the substrate layer and 25%-30% in the composite layer.

[0078] The microcapsule particles of the present invention have a wall material coverage rate of ≥85% and a wall material thickness of 20-40μm.

[0079] The fireproof board of the present invention is used in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

[0080] A fireproof board for a new energy battery compartment is prepared from the fireproof board of the present invention.

[0081] A fireproof partition wall panel for buildings, prepared from the fireproof panel of this invention.

[0082] The present invention has the following beneficial effects: I. Core collaborative system design of this invention: 1. Material system matching (1) Microcapsules: wall material APP-MF (pyrolyzes at above 200℃, APP decomposes to produce phosphoric acid to catalyze the breakage of MF cross-linking bonds); core material aminosulfonic acid (acidic, decomposition temperature 205℃) + ammonium bicarbonate (alkaline, decomposition temperature 150℃) + nano montmorillonite (dispersant). The core material is covered and isolated by APP-MF wall material to avoid low-temperature reaction with the layer structure.

[0083] (2) Substrate layer: Magnesium hydroxide is the core component, which has both flame retardancy and reactivity. It reacts with aminosulfonic acid in the core material to produce gas, and at the same time decomposes and absorbs heat to cool down.

[0084] (3) Fireproof surface layer: expandable graphite (expansion temperature 200℃) undergoes intercalation reaction with the core material aminosulfonic acid, promoting rapid expansion of graphite and capturing gas to prevent diffusion.

[0085] 2. Core Logic of Synergy After the microcapsule wall material breaks at temperatures above 200°C, the core material is released and forms a "three-level reaction chain" with the substrate layer and the fireproof surface layer. This not only amplifies the gas production but also locks the gas in place through the interlayer structure, enhancing the fire extinguishing effect and solving the shortcomings of traditional microcapsules, such as "easy gas dissipation and limited fire extinguishing capabilities".

[0086] II. Interlayer Synergistic Effect and Fire Extinguishing Principle: 1. First layer of synergy: "Gas generation-cooling" synergy between the core material and the substrate layer: (1) Reaction process: The aminosulfonic acid (H2NSO3H) released by the microcapsule core material reacts with the magnesium hydroxide (Mg(OH)2) in the substrate layer in an acid-base reaction:

[0087] Meanwhile, ammonium bicarbonate in the core material undergoes pyrolysis:

[0088] In the core material, aminosulfonic acid further catalyzes the reaction of NH3 with trace amounts of moisture in the substrate layer to generate N2.

[0089] (2) Fire extinguishing principle: Enhanced gas production: The acid-base reaction generates additional H2O, which, combined with the gas produced by the pyrolysis of ammonium bicarbonate, increases the gas production by at least 30% compared to a single core material. Cooling Synergy: The decomposition of magnesium hydroxide (above 200℃) absorbs a large amount of heat (1 mol Mg(OH)2 absorbs 184 kJ of heat), which is superimposed with the heat absorption of gaseous H2O evaporation, causing the fire temperature to drop by 80-100℃ within 1 minute, thus disrupting the combustion temperature conditions.

[0090] Optimization effect: Avoids "gas overheating and diffusion" caused by single gas production, the cooling effect prolongs the gas residence time, and the asphyxiation efficiency inside the fireproof board is increased by 50%.

[0091] 2. Second layer of synergy: The "gas generation-sealing" synergy between the core material and the fire-resistant surface layer: (1) Reaction process: The aminosulfonic acid released by the core material acts as an intercalating agent, which reacts with the expandable graphite of the fireproof surface layer, destroying the interlayer force of graphite and causing the graphite to expand rapidly at 200°C (expansion ratio ≥ 30 times); at the same time, the gas volume expansion of the core material pushes the graphite expansion body to evenly cover the surface and gaps of the fireproof board.

[0092] (2) Fire extinguishing principle: Gas locking: Expanded graphite forms a dense, porous carbon layer, which acts like a "gas cage" to trap the CO2-N2-H2O mixture, preventing the gas from diffusing rapidly and keeping the oxygen concentration in the protective space formed by the fireproof board below 12%. Physical isolation: The char layer simultaneously isolates combustibles from contact with oxygen and heat, thus interrupting the combustion chain.

[0093] (3) Optimization effect: To solve the problem of traditional microcapsule gas production simply dissipating, the gas residence time has been extended from 30 seconds to 120 seconds, increasing the success rate of fire extinguishing in confined spaces from 70% to 100%.

[0094] 3. The third synergy: the "flame retardant-reinforcement" synergy of microcapsule residue-layer structure: (1) Reaction process: After the microcapsule wall material APP-MF is pyrolyzed, polyphosphate residue is generated, which is mixed with the magnesium hydroxide decomposition product MgO of the substrate layer and the graphite expansion body of the fireproof surface layer to form a composite flame-retardant coating of "polyphosphate-MgO-carbon layer".

[0095] (2) Fire extinguishing principle: Melt coating: The composite flame-retardant coating melts at high temperatures in a fire, enveloping the surface of combustibles and preventing the volatilization of combustible gases; Catalytic char formation: Ammonium polyphosphate salts catalyze the organic components of the substrate layer to form char, further enhancing the barrier effect.

[0096] (3) Optimization effect: The composite flame-retardant coating formed after fire extinguishing reduces the reignition rate of the fireproof board to 0, while the reignition rate of the traditional fireproof board without synergistic design (model CS195) is 35%.

[0097] 4. Fourth level of synergy: Gas flow-interlayer pore “uniform coverage” synergy: (1) Reaction process: Each layer of the fireproof board has a pre-set micron-level pore (15%-20% porosity of the substrate layer and 25%-30% porosity of the composite layer). After the microcapsules generate gas, it diffuses evenly along the pores to avoid the problems of excessively high local gas concentration and insufficient local gas concentration.

[0098] (2) Fire extinguishing principle: Gas permeates through the pores to all areas of the fireproof board, achieving "all-round suffocation", especially for fire sources in hidden gaps.

[0099] (3) Optimization effect: The fireproof board reduces the fire extinguishing dead angle by 80%, and is suitable for fire protection of complex structures (such as fireproof boards for new energy battery compartments, fireproof boards for building partitions, etc.). Attached Figure Description

[0100] Figure 1 The image shows the expansion of expandable graphite in the fireproof board of the present invention during a fire. Figure 2 This is an image of the polyphosphate ammonium salt-MgO-carbon layer composite flame retardant coating of the present invention. Detailed Implementation

[0101] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Example 1

[0102] A fireproof board comprises, from the inside out, a substrate layer, a microcapsule composite layer, and a fireproof surface layer.

[0103] The substrate layer comprises the following raw materials: 35 parts by weight of modified magnesium hydroxide, 60 parts by weight of modified calcium carbonate, 10 parts by weight of pre-thickened styrene-acrylic emulsion, and 6 parts by weight of talc.

[0104] The microcapsule composite layer comprises the following raw materials: 70 parts by weight of modified talc, 20 parts by weight of microcapsule suspension (dry surface-modified microcapsules), 8 parts by weight of water-based styrene-acrylic emulsion, and 1.5 parts by weight of ethylene glycol butyl ether.

[0105] The fireproof surface layer comprises the following raw materials: 18 parts by weight of intercalated modified expandable graphite, 80 parts by weight of modified epoxy resin, 3 parts by weight of modified nano silica, and 4 parts by weight of silane coupling agent KH550.

[0106] The preparation method of microcapsules is as follows: The microcapsules in this embodiment are prepared using a four-stage process: core material pretreatment, wall material modification, stepwise encapsulation, and post-crosslinking reinforcement, as detailed below: S1. Raw material pretreatment S11. Core Material Pretreatment S111. Aminosulfonic acid (purity ≥99.5%): Processed by air jet milling with an inlet pressure of 0.7 MPa and a milling time of 25 min. The powder with a particle size of 5-10 μm was collected by passing it through a 500-mesh standard sieve and placed in a vacuum drying oven at 70℃ for 5 h to remove surface adsorbed water and prevent subsequent agglomeration.

[0107] S112. Ammonium bicarbonate (purity ≥99.0%): dried under low temperature vacuum at 45℃ and -0.085MPa for 7 hours. After crushing, it is passed through a 400-mesh sieve to control the particle size to 10-20μm and avoid premature decomposition at high temperature.

[0108] S113. Nano-montmorillonite (particle size 5-10nm): Nano-montmorillonite and hexadecyltrimethylammonium bromide are mixed at a mass ratio of 10:1.5, deionized water is added (solid-liquid ratio 1:25, unit is g / L), stirred at 85℃ for 2.5h, centrifuged (speed 3500r / min, time 18min), the precipitate is vacuum dried at 65℃ for 10h, and ground through a 400-mesh sieve to improve compatibility with organic core materials.

[0109] S12. Pretreatment of wall material raw materials S121. Ammonium polyphosphate (APP, degree of polymerization n=1200, phosphorus content 35%): APP was added to an ethanol-water mixture (ethanol to water volume ratio 7:3), solid-liquid ratio 1:20, and 4wt% (4wt% of the total mass of APP and ethanol-water mixture) of γ-glycidoxypropyltrimethoxysilane (KH-560) was added. The mixture was stirred at 65℃ for 3.5h, and the solvent was removed by vacuum distillation (temperature 55℃, vacuum degree -0.075MPa). The mixture was then vacuum dried at 55℃ for 5h to obtain modified APP, which improves the reactivity of APP with MF resin.

[0110] S122. Preparation of melamine-formaldehyde resin (MF) prepolymer: The formaldehyde solution (mass fraction 37%) was placed in a reaction vessel at a formaldehyde to melamine molar ratio of 2.8:1. The pH was adjusted to 8.5, melamine was added, and the mixture was stirred at 45°C for 35 min until completely dissolved. The temperature was then raised to 75°C and reacted for 75 min to obtain an MF prepolymer with a solid content of 35%. The prepolymer was cooled to room temperature for later use, and the degree of hydroxymethylation was controlled at 65%.

[0111] S2. Core Material Preparation S21. Primary mixing: Place the pretreated aminosulfonic acid and ammonium bicarbonate in a mass ratio of 3:5.5 in a double planetary mixer, add 2.5wt% (accounting for 2.5wt% of the total mass of the core material) of polyethylene glycol (PEG-6000) as a dispersant, and stir at low speed (400r / min) for 25min to initially mix evenly.

[0112] S22. Secondary dispersion: Add pretreated nano-montmorillonite (accounting for 18% of the total mass of the core material), heat to 75℃, stir at high speed (1800 r / min) for 50 min, and at the same time purge nitrogen (flow rate 0.8 L / min) for protection to avoid oxidative decomposition of ammonium bicarbonate.

[0113] S23. Granulation and molding: The mixed slurry is added to a spray dryer with an inlet air temperature of 170℃, an outlet air temperature of 80℃, an atomization pressure of 0.4MPa, and a feed rate of 25mL / min to obtain the initial core material particles.

[0114] S24. Grading and screening: The initial core material particles after spray drying are screened by an air classifier at a grading pressure of 0.5 MPa. Core material particles with a particle size of 30-50 μm are collected, and the particle size distribution range is controlled within 1.2-1.5 to ensure the uniformity of subsequent coating.

[0115] S25. Core material stabilization treatment: The screened core material is placed in a constant temperature and humidity chamber and aged for 36 hours at a temperature of 35℃ and a relative humidity of 45% to eliminate internal stress and improve the storage stability of the core material.

[0116] S3. Wall material preparation S31. Preparation of basic emulsion: Mix modified APP and MF prepolymer at a mass ratio of 5:6, add ethanol as solvent, solid-liquid ratio of 1:10, adjust pH=8.0, stir at 55℃ for 75min at a speed of 1000r / min to form a uniform wall material basic emulsion.

[0117] S32. Crosslinking agent adjustment: Add adipate dihydrazide equivalent to 6% of the mass of MF prepolymer as a crosslinking agent, continue stirring for 35 min, control the crosslinking degree of the wall material emulsion and the precursor content to 30%, and ensure the density of the wall material after subsequent coating.

[0118] S33. Emulsion stabilization: Add polyvinyl alcohol (PVA-1788) equivalent to 0.8 wt% of the MF prepolymer as a stabilizer, ultrasonically disperse (power 400W, time 18min) to eliminate emulsion bubbles, let stand for 25min, take the upper homogeneous emulsion for later use, and control the emulsion solid content at room temperature to 28% and the viscosity to 650mPa•s.

[0119] S4. Coating reaction S41. Pre-coating stage: Add the stabilized wall material emulsion to the reactor, introduce nitrogen gas (flow rate 1.2L / min), add the core material particles after classification and screening, with a core material particle to wall material emulsion mass ratio of 1:4, adjust pH=8.0, heat to 50℃, stir at low speed (200r / min) for 35min, and simultaneously use ultrasonic-assisted dispersion (power 250W, intermittent ultrasonic: work for 5min, pause for 3min, cycle 4 times) to make the core material particles uniformly dispersed in the wall material emulsion, forming a primary coating system.

[0120] S42. In-situ polymerization stage: The temperature is increased in stages. In the first stage, the temperature is increased to 62℃ at a rate of 1.5℃ / min, the stirring speed is increased to 600r / min, and the reaction is carried out for 75min to promote the initial polymerization of the wall material on the surface of the core material. In the second stage, the temperature is increased to 72℃, the stirring speed is increased to 900r / min, and the reaction is carried out for 100min to form a dense three-dimensional network structure of the wall material. During the reaction, the coating thickness is sampled and tested every 30min to control the thickness of the primary wall material to 25μm.

[0121] S43. Post-crosslinking stage: Add melamine equivalent to 4% of the total mass of the wall material as a crosslinking agent, adjust the pH to 7.0, keep at 78℃ for 70 minutes to strengthen the crosslinking structure of the wall material and improve its thermal stability and sealing performance.

[0122] S5. Post-processing technology S51. Washing and purification: Centrifuge the encapsulated microcapsule suspension (5000 r / min, 25 min), remove the supernatant, wash 4 times with an ethanol-water mixture (volume ratio 1:1) to remove unreacted monomers and free wall material; then wash 2 times with deionized water to remove residual ethanol and ensure that there are no impurities on the surface of the microcapsules.

[0123] S52. Freeze-drying: Place the washed microcapsules in a freeze dryer, pre-freeze at -45℃ for 3 hours, then adjust the vacuum to 15Pa, raise the temperature to -5℃, and dry for 30 hours to avoid the core material decomposition or wall material deformation caused by high temperature, and obtain a loose and dry microcapsule intermediate.

[0124] S53. Surface-modified microcapsules: Add the microcapsule intermediate to an ethanol solution at a solid-liquid ratio of 1:12, add KH-550 silane coupling agent at 1.5 wt% of the microcapsule intermediate, stir at 55°C for 75 min, centrifuge (3500 r / min, 18 min), and vacuum dry at 55°C for 5 h to improve the compatibility and bonding strength between the microcapsules and the various layers of the fireproof board.

[0125] S54. Grading and Quality Control: The surface-modified microcapsules are screened by a vibrating screen with a pore size of 80-120μm to remove oversized or undersized particles and ensure uniform microcapsule size; random samples are taken to test the encapsulation rate (≥85%), wall thickness (30μm), and thermal decomposition temperature (200-230℃). Unqualified products are returned to the washing process for reprocessing.

[0126] S55. Stabilization storage: Place qualified microcapsules in a vacuum packaging container, add desiccant (montmorillonite desiccant, 6% of the mass of the microcapsules), and store in an environment with a temperature of 25℃ and a relative humidity of 60%. Shelf life is ≥12 months.

[0127] A method for preparing a fireproof board according to the present invention includes the following steps: The fireproof board of this invention adopts a five-stage preparation process: layered preparation, interface modification, stepwise composite, gradient curing, and post-treatment strengthening, as detailed below: S1. Pretreatment of raw materials for each layer of fireproof board S11. Pretreatment of substrate material S111. Magnesium hydroxide (purity ≥98%, initial particle size 10-50μm): Surface activation modification is performed by mixing magnesium hydroxide and stearic acid at a mass ratio of 100:3, adding ethanol solution (solid-liquid ratio 1:12), stirring at 75℃ for 2.5h, centrifuging (3500r / min, 18min), drying the precipitate under vacuum at 90℃ for 5h, grinding it through a 300-mesh sieve, and controlling the particle size after modification to 10-20μm to improve compatibility and dispersion uniformity with adhesives.

[0128] S112. Calcium carbonate (heavy, whiteness ≥93%): After wet ultrafine grinding, calcium carbonate and deionized water are mixed at a mass ratio of 1:4, and sodium hexametaphosphate dispersant equivalent to 0.8wt% of calcium carbonate is added. The grinding speed is 2500r / min and the grinding time is 75min. The powder is spray-dried (inlet air 190℃, outlet air 85℃), and the powder with a particle size of 5-15μm is collected and dried at 65℃ for 3.5h for later use.

[0129] S113. Aqueous styrene-acrylic emulsion (solid content 45%): Pre-thickening treatment, add 0.4wt% of hydroxyethyl cellulose to the aqueous styrene-acrylic emulsion, stir at 55℃ for 35min, adjust the viscosity to 1800mPa•s (25℃) to avoid sagging during coating.

[0130] S12. Pretreatment of raw materials for microcapsule composite layers S121. Inorganic filler (talc powder, particle size 5-10μm): Silane modification is performed by mixing talc powder with KH-550 silane coupling agent at a mass ratio of 100:1.5, adding an ethanol-water mixed solution (the volume ratio of ethanol to water in the ethanol-water mixed solution is 6:4), with a solid-liquid ratio of 1:15, stirring at 65℃ for 2.5h, removing the solvent by vacuum distillation, and drying at 75℃ for 4.5h to improve the binding force with microcapsules and adhesives.

[0131] S122. Pretreated microcapsules: For polydispersion treatment, surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:6, and 0.25wt% (equivalent to 0.25wt% of the total mass of microcapsules and deionized water) of polyethylene glycol (PEG-4000) is added. The mixture is then ultrasonically dispersed (power 300W, time 12min) to form a stable suspension and prevent microcapsule aggregation in the composite layer.

[0132] S13. Pretreatment of fire-resistant surface material S131. Expandable graphite (expansion ratio ≥30 times, particle size 20-50μm, model: SGL carbon, manufacturer: SGL Graphite, Germany): Mix expandable graphite and phosphoric acid at a mass ratio of 10:2, stir at 65℃ for 75 min, wash with deionized water until pH=6.5, centrifuge (4000 r / min, 12 min), and vacuum dry at 85℃ for 7 h to improve the expansion rate and compatibility with resin.

[0133] S132. Epoxy resin (E-44): Dilute and modify, add acetone (epoxy resin to acetone volume ratio 1:0.4), stir at 45℃ for 35 min, add 2.5 wt% (equivalent to 2.5 wt% of the total mass of epoxy resin and acetone) of triethylenetetramine curing agent, stir for 18 min, and adjust the viscosity to 1000 mPa•s (25℃).

[0134] S133. Nano silica (particle size 10-20nm): Hydrophobic modification, nano silica and methyltriethoxysilane are mixed at a mass ratio of 100:4, toluene solution is added (solid-liquid ratio 1:25), refluxed and stirred at 85℃ for 3.5h, filtered and dried at 95℃ for 5.5h to improve the surface wear resistance and self-cleaning performance.

[0135] S2. Individual preparation process for each layer S21. Substrate layer preparation S211. Primary mixing: Place 35 parts of modified magnesium hydroxide, 60 parts of modified calcium carbonate, 10 parts of pre-thickened styrene-acrylic emulsion, and 6 parts of talc into a high-speed kneader and stir at low speed (400 r / min) for 25 min to initially mix evenly.

[0136] S212. Secondary kneading: Heat to 65℃, stir at high speed (1200r / min) for 50min, and simultaneously introduce nitrogen (flow rate 0.4L / min) to remove air bubbles generated during the mixing process, thereby obtaining a uniform substrate slurry.

[0137] S213. Roll forming: The slurry is fed into a two-roll mill with a roll temperature of 75°C, a roll speed of 25 r / min, and a rolling gap of 10 mm. After 4 rolling passes, the thickness of the substrate layer is controlled to 10 mm to ensure a dense structure (porosity of 15%-20%).

[0138] S214. Pre-curing: Place the rolled substrate layer in a constant temperature oven and pre-cur it at 85°C for 2.5 hours to remove some moisture and volatile components, improve the strength of the substrate layer, and prevent deformation during subsequent lamination.

[0139] S22. Preparation of microcapsule composite layer S221. Mixing and Dispersion: Place 70 parts of modified talc powder, 20 parts of microcapsule suspension (dry surface-modified microcapsules), 8 parts of aqueous styrene-acrylic emulsion, and 1.5 parts of film-forming aid (ethylene glycol butyl ether) into a planetary mixer. First, stir at low speed (600 rpm) for 35 min, then stir at high speed (1800 rpm) for 75 min. Simultaneously, perform ultrasonic-assisted dispersion (power 400W, intermittent: 10 min operation, 5 min pause, 3 cycles) to ensure uniform dispersion of microcapsules (distribution density 50-80 particles / mm²). 2 ).

[0140] S222. Interface treatment: Coat the surface of the pre-cured substrate layer with a layer of coupling agent dilution (KH-550 and ethanol volume ratio 1:10), coating amount 6g / m². 2 After being placed at room temperature for 45 minutes, the substrate surface is activated, and the adhesion between the substrate and the microcapsule composite layer is improved (peel strength ≥ 1.5 N / mm).

[0141] S223. Slit Extrusion Coating: The microcapsule composite layer slurry is coated onto the surface of the substrate layer using a slit extrusion coating machine. The coating temperature is 55℃, the coating speed is 0.8m / min, and the coating thickness is 3mm. The thickness deviation is controlled within ±0.1mm by real-time monitoring with a laser thickness gauge.

[0142] S224. Semi-curing: The coated board is placed in a constant temperature and humidity chamber at 65℃ and 55% relative humidity for 1.5 hours to allow the composite layer to initially form and prevent the slurry from penetrating during subsequent surface coating.

[0143] The porosity of the microcapsule composite layer obtained above is 25%-30%.

[0144] S23 fire-resistant surface preparation S231. Preparation of surface slurry: 18 parts of intercalated modified expandable graphite, 80 parts of modified epoxy resin, 3 parts of modified nano silica, and 4 parts of coupling agent are placed in a high-speed disperser and stirred at 65°C for 75 min at a speed of 1500 r / min to form a uniform surface slurry (solid content 65%).

[0145] S232. Composite layer interface activation: Plasma treatment is performed on the surface of the semi-cured microcapsule composite layer. The plasma power is 120W, the treatment time is 4min, and the treatment distance is 8mm to improve the bonding force between the surface layer and the composite layer (peel strength ≥1.2N / mm).

[0146] S233. Doctor blade coating: The surface slurry is coated onto the surface of the microcapsule composite layer using a comma doctor blade coating machine. The coating angle is 35°, the coating speed is 0.5 m / min, and the coating thickness is 3 mm. After coating, the surface is smoothed a second time with a doctor blade roller to ensure the surface smoothness (surface roughness Ra≤1.0μm).

[0147] S234. Pre-drying: Place the coated board in a hot air circulating oven and pre-dry at 75°C for 2.5 hours to remove solvent and moisture, and avoid the formation of bubbles or pinholes during curing.

[0148] S3. Interlayer lamination and gradient curing process S31. Layer positioning: Place the pre-dried board on the hot press workbench and fix it with positioning pins to ensure that each layer is aligned (edge ​​deviation ≤ 0.5mm) to avoid misalignment between layers affecting the synergistic effect.

[0149] S32. Stepwise hot pressing curing S321. First stage (preheating and pressurization): Heat to 110℃ at a rate of 2.5℃ / min, apply pressure of 4MPa, and maintain the temperature and pressure for 75min to promote the initial cross-linking of each layer of adhesive and enhance the interlayer bonding.

[0150] S322. Second stage (heating and curing): Continue to heat to 160℃ at a rate of 1.5℃ / min, increase the pressure to 7MPa, and hold at the temperature and pressure for 150min to ensure that each layer is completely cured, while ensuring that the microcapsule wall material is not damaged (the hot pressing temperature is 20-30℃ lower than the microcapsule decomposition temperature).

[0151] S323. Third stage (cooling and pressure relief): Cool down to 90℃ at a rate of 1.5℃ / min, reduce the pressure to 2.5MPa, maintain the temperature and pressure for 45min to eliminate internal stress; then cool down naturally to room temperature, release the pressure and remove the board to avoid cracking of the board due to excessive cooling.

[0152] S324. Post-curing treatment: The hot-pressed board is placed in a constant temperature oven and cured at 130℃ for 5 hours to further improve the cross-linking degree of each layer and the overall mechanical properties, so that the fireproof board has a bending strength of 25MPa and a compressive strength of 32MPa.

[0153] S4. Post-processing and quality control technology S41. Cutting and finishing: The board is cut to length using a CNC cutting machine at a speed of 1.5m / min and a cutting accuracy of ±0.2mm. Edge burrs and irregular parts are removed to ensure that the board size meets the design requirements.

[0154] S42. Surface polishing: Polish the surface with 200-grit sandpaper at a speed of 4 m / min and a pressure of 0.2 MPa to make the surface smooth and flat, while removing residual impurities.

[0155] S43. Aging treatment: Place the sanded board in an aging test chamber at a temperature of 70℃ and a relative humidity of 90% for 100 hours.

[0156] S44. Performance testing: Conduct appearance inspection, dimensional inspection, mechanical testing, and fire extinguishing performance testing on the product.

[0157] Appearance inspection: The surface is free of cracks, bubbles, and missing materials, and the color is uniform; Dimensional inspection: thickness deviation ±0.3mm, length / width deviation ±0.5mm; Mechanical testing: flexural strength 25MPa, compressive strength 32MPa, interlaminar peel strength 1.6N / mm; Fire extinguishing performance test: After being triggered at 200℃, the gas production rate is 2.0L / (g・min) within 30 seconds, the oxygen concentration drops to below 10%, and there is no reignition after extinguishing the fire.

[0158] S45. Packaging and Storage: Qualified boards are packaged with waterproof film and pearl cotton to avoid damage during transportation; they are stored in a warehouse with a temperature of 25℃ and a relative humidity of 60%, away from fire sources and high-temperature environments, with a storage period of ≥12 months.

[0159] The fireproof board in this embodiment is used in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

[0160] A fireproof board for a new energy battery compartment is prepared from the fireproof board of this embodiment.

[0161] A fireproof partition wall panel for buildings is prepared from the fireproof panel of this embodiment.

[0162] like Figure 1 As shown, this embodiment illustrates the appearance of the fireproof board under fire conditions, where the expandable graphite expands; the darker color represents the expanded graphite. Figure 2 As shown, in the event of a fire, the microcapsule wall material APP-MF of this embodiment undergoes pyrolysis to generate polyphosphate residue, which is mixed with the magnesium hydroxide decomposition product MgO of the substrate layer and the graphite expansion body of the fireproof surface layer to form a composite flame-retardant coating of "polyphosphate-MgO-carbon layer". Example 2

[0163] A fireproof board comprises, from the inside out, a substrate layer, a microcapsule composite layer, and a fireproof surface layer.

[0164] The substrate layer comprises the following raw materials: 30 parts by weight of modified magnesium hydroxide, 55 parts by weight of modified calcium carbonate, 8 parts by weight of pre-thickened styrene-acrylic emulsion, and 5 parts by weight of talc.

[0165] The microcapsule composite layer comprises the following raw materials: 65 parts by weight of modified talc, 18 parts by weight of microcapsule suspension (dry surface-modified microcapsules), 7 parts by weight of water-based styrene-acrylic emulsion, and 1 part by weight of ethylene glycol butyl ether.

[0166] The fireproof surface layer comprises the following raw materials: 15 parts by weight of intercalated modified expandable graphite, 75 parts by weight of modified epoxy resin, 2 parts by weight of modified nano silica, and 3 parts by weight of silane coupling agent KH550.

[0167] The preparation method of microcapsules is as follows: The microcapsules in this embodiment are prepared using a four-stage process: core material pretreatment, wall material modification, stepwise encapsulation, and post-crosslinking reinforcement, as detailed below: S1. Raw material pretreatment S11. Core Material Pretreatment S111. Aminosulfonic acid (purity ≥99.5%): Processed by air jet milling with an inlet pressure of 0.6 MPa and a milling time of 20 min. The powder with a particle size of 5-10 μm was collected by passing it through a 400-mesh standard sieve and placed in a vacuum drying oven at 60℃ for 4 h to remove surface adsorbed water and prevent subsequent agglomeration.

[0168] S112. Ammonium bicarbonate (purity ≥99.0%): dried under low temperature vacuum at 40℃ and -0.08MPa for 6 hours. After crushing, it is passed through a 300-mesh sieve to control the particle size to 10-20μm to avoid premature decomposition at high temperature.

[0169] S113. Nano-montmorillonite (particle size 5-10nm): Nano-montmorillonite and hexadecyltrimethylammonium bromide are mixed at a mass ratio of 10:1, deionized water is added (solid-liquid ratio 1:20, unit is g / L), stirred at 80℃ for 2h, centrifuged (speed 3000r / min, time 15min), the precipitate is vacuum dried at 60℃ for 8h, and ground through a 300-mesh sieve to improve compatibility with organic core materials.

[0170] S12. Pretreatment of wall material raw materials S121. Ammonium polyphosphate (APP, degree of polymerization n=1000, phosphorus content 30%): APP was added to an ethanol-water mixture (ethanol to water volume ratio 7:3), solid-liquid ratio 1:15, and 3wt% (3wt% of the total mass of APP and ethanol-water mixture) of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was added. The mixture was stirred at 60℃ for 3h, and the solvent was removed by vacuum distillation (temperature 50℃, vacuum degree -0.07MPa). The mixture was then vacuum dried at 50℃ for 4h to obtain modified APP, which improves the reactivity of APP with MF resin.

[0171] S122. Preparation of melamine-formaldehyde resin (MF) prepolymer: The formaldehyde solution (mass fraction 37%) was placed in a reaction vessel at a formaldehyde to melamine molar ratio of 2.5:1. The pH was adjusted to 8.5, melamine was added, and the mixture was stirred at 40°C for 30 min until completely dissolved. The temperature was then raised to 70°C and reacted for 60 min to obtain an MF prepolymer with a solid content of 30%. The prepolymer was cooled to room temperature for later use, and the degree of hydroxymethylation was controlled at 60%.

[0172] S2. Core Material Preparation S21. Primary mixing: Place the pretreated aminosulfonic acid and ammonium bicarbonate in a double planetary mixer at a mass ratio of 3:5, add 2wt% (accounting for 2wt% of the total mass of the core material) of polyethylene glycol (PEG-6000) as a dispersant, and stir at low speed (300 r / min) for 20 min to initially mix evenly.

[0173] S22. Secondary dispersion: Add pretreated nano-montmorillonite (15% of the total mass of the core material), heat to 70℃, stir at high speed (1500 r / min) for 40 min, and at the same time purge nitrogen (flow rate 0.5 L / min) for protection to avoid oxidative decomposition of ammonium bicarbonate.

[0174] S23. Granulation and molding: The mixed slurry is added to a spray dryer with an inlet air temperature of 160℃, an outlet air temperature of 70℃, an atomization pressure of 0.3MPa, and a feed rate of 20mL / min to obtain the initial core material particles.

[0175] S24. Grading and screening: The initial core material particles after spray drying are screened by an air classifier at a grading pressure of 0.4 MPa. Core material particles with a particle size of 30-50 μm are collected, and the particle size distribution range is controlled within 1.2-1.5 to ensure the uniformity of subsequent coating.

[0176] S25. Core material stabilization treatment: The screened core material is placed in a constant temperature and humidity chamber and matured for 24 hours at a temperature of 30℃ and a relative humidity of 40% to eliminate internal stress and improve the storage stability of the core material.

[0177] S3. Wall material preparation S31. Preparation of basic emulsion: Modified APP and MF prepolymer are mixed at a mass ratio of 4:6, ethanol is added as solvent, the solid-liquid ratio is 1:8, the pH is adjusted to 7.5, and the mixture is stirred at 50℃ for 60 min at a speed of 800 r / min to form a uniform wall material basic emulsion.

[0178] S32. Crosslinking agent adjustment: Add adipate dihydrazide equivalent to 5% of the mass of MF prepolymer as a crosslinking agent, continue stirring for 30 minutes, control the crosslinking degree of the wall material emulsion and the precursor content to 25%, and ensure the density of the wall material after subsequent coating.

[0179] S33. Emulsion stabilization: Add polyvinyl alcohol (PVA-1788) equivalent to 0.5 wt% of the MF prepolymer as a stabilizer, ultrasonically disperse (300W power, 15min time) to eliminate emulsion bubbles, let stand for 20min, take the upper homogeneous emulsion for later use, and control the emulsion solid content at room temperature to 25% and the viscosity to 500mPa•s.

[0180] S4. Coating reaction S41. Pre-coating stage: Add the stabilized wall material emulsion to the reactor, introduce nitrogen gas (flow rate 1.0 L / min), add the core material particles after classification and screening, with a core material particle to wall material emulsion mass ratio of 1:3, adjust pH=8.0, heat to 45℃, stir at low speed (200 r / min) for 30 min, and simultaneously use ultrasonic-assisted dispersion (power 200 W, intermittent ultrasonic: work for 5 min, pause for 3 min, cycle 3 times) to make the core material particles uniformly dispersed in the wall material emulsion, forming a primary coating system.

[0181] S42. In-situ polymerization stage: The temperature is increased in stages. In the first stage, the temperature is increased to 60°C at a rate of 1°C / min, the stirring speed is increased to 500 r / min, and the reaction is carried out for 60 min to promote the initial polymerization of the wall material on the surface of the core material. In the second stage, the temperature is increased to 70°C, the stirring speed is increased to 800 r / min, and the reaction is carried out for 90 min to form a dense three-dimensional network structure of the wall material. During the reaction, the coating thickness is sampled and tested every 30 min to control the thickness of the primary wall material to 20 μm.

[0182] S43. Post-crosslinking stage: Add melamine equivalent to 3% of the total mass of the wall material as a crosslinking agent, adjust the pH to 7.0, keep at 75℃ for 60 minutes to strengthen the crosslinking structure of the wall material and improve its thermal stability and sealing performance.

[0183] S5. Post-processing technology S51. Washing and purification: Centrifuge the encapsulated microcapsule suspension (4000 r / min, 20 min), remove the supernatant, wash 3 times with an ethanol-water mixture (volume ratio 1:1) to remove unreacted monomers and free wall material; then wash 2 times with deionized water to remove residual ethanol and ensure that there are no impurities on the surface of the microcapsules.

[0184] S52. Freeze-drying: Place the washed microcapsules in a freeze dryer, pre-freeze at -40℃ for 2 hours, then adjust the vacuum to 10Pa, raise the temperature to -10℃, and dry for 24 hours to avoid the core material decomposition or wall material deformation caused by high temperature, and obtain a loose and dry microcapsule intermediate.

[0185] S53. Surface-modified microcapsules: Add the microcapsule intermediate to an ethanol solution with a solid-liquid ratio of 1:10, add KH-550 silane coupling agent equivalent to 1 wt% of the mass of the microcapsule intermediate, stir at 50°C for 60 min, centrifuge (3000 r / min, 15 min), and vacuum dry at 50°C for 4 h to improve the compatibility and bonding force between the microcapsules and the various layers of the fireproof board.

[0186] S54. Grading and Quality Control: The surface-modified microcapsules are screened by a vibrating screen with a pore size of 80-120μm to remove oversized or undersized particles and ensure uniform microcapsule size; random samples are taken to test the encapsulation rate (≥85%), wall thickness (20μm), and thermal decomposition temperature (200-230℃). Unqualified products are returned to the washing process for reprocessing.

[0187] S55. Stabilization storage: Place qualified microcapsules in a vacuum packaging container, add desiccant (montmorillonite desiccant, 5% of the mass of the microcapsules), and store in an environment with a temperature of 20℃ and a relative humidity of 50%. Shelf life is ≥12 months.

[0188] A method for preparing a fireproof board according to the present invention includes the following steps: The fireproof board of this invention adopts a five-stage preparation process: layered preparation, interface modification, stepwise composite, gradient curing, and post-treatment strengthening, as detailed below: S1. Pretreatment of raw materials for each layer of fireproof board S11. Pretreatment of substrate material S111. Magnesium hydroxide (purity ≥98%, initial particle size 10-50μm): Surface activation modification is performed by mixing magnesium hydroxide and stearic acid at a mass ratio of 100:2, adding ethanol solution (solid-liquid ratio 1:10), stirring at 70℃ for 2h, centrifuging (3000r / min, 15min), drying the precipitate under vacuum at 80℃ for 4h, grinding it through a 300-mesh sieve, controlling the particle size after modification to 10-20μm, improving compatibility and dispersion uniformity with adhesives.

[0189] S112. Calcium carbonate (heavy, whiteness ≥93%): After wet ultrafine grinding, calcium carbonate and deionized water are mixed at a mass ratio of 1:3, and sodium hexametaphosphate dispersant equivalent to 0.5wt% of calcium carbonate is added. The grinding speed is 2000r / min and the grinding time is 60min. The powder is spray-dried (inlet air 180℃, outlet air 80℃), and the powder with a particle size of 5-15μm is collected and dried at 60℃ for 3h for later use.

[0190] S113. Aqueous styrene-acrylic emulsion (solid content 40%): Pre-thickening treatment, add 0.3wt% of hydroxyethyl cellulose to the aqueous styrene-acrylic emulsion, stir at 50℃ for 30min, adjust the viscosity to 1500mPa•s (25℃) to avoid sagging during coating.

[0191] S12. Pretreatment of raw materials for microcapsule composite layers S121. Inorganic filler (talc powder, particle size 5-10μm): Silane modification is performed by mixing talc powder with KH-550 silane coupling agent at a mass ratio of 100:1, adding an ethanol-water mixed solution (the volume ratio of ethanol to water in the ethanol-water mixed solution is 6:4), with a solid-liquid ratio of 1:11, stirring at 60℃ for 2h, removing the solvent by vacuum distillation, and drying at 70℃ for 4h to improve the binding force with microcapsules and adhesives.

[0192] S122. Pretreated microcapsules: For the re-dispersion treatment, the surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:5, and 0.2wt% (equivalent to 0.2wt% of the total mass of microcapsules and deionized water) of polyethylene glycol (PEG-4000) is added. The mixture is then ultrasonically dispersed (power 300W, time 10min) to form a stable suspension and prevent the microcapsules in the composite layer from agglomerating.

[0193] S13. Pretreatment of fire-resistant surface material S131. Expandable graphite (expansion ratio ≥30 times, particle size 20-50μm, model: SGL carbon, manufacturer: SGL Graphite, Germany): Mix expandable graphite and phosphoric acid at a mass ratio of 10:1, stir at 60℃ for 60 min, wash with deionized water until pH=6, centrifuge (3000 r / min, 10 min), and vacuum dry at 80℃ for 6 h to improve the expansion rate and compatibility with resin.

[0194] S132. Epoxy resin (E-44): Dilute and modify, add acetone (epoxy resin to acetone volume ratio 1:0.3), stir at 40℃ for 30 min, add 2 wt% (equivalent to 2 wt% of the total mass of epoxy resin and acetone) of triethylenetetramine curing agent, stir for 15 min, and adjust the viscosity to 800 mPa•s (25℃).

[0195] S133. Nano silica (particle size 10-20nm): Hydrophobic modification, nano silica and methyltriethoxysilane are mixed at a mass ratio of 100:3, toluene solution is added (solid-liquid ratio 1:20), refluxed and stirred at 80℃ for 3h, filtered and dried at 90℃ for 5h to improve the surface wear resistance and self-cleaning performance.

[0196] S2. Individual preparation process for each layer S21. Substrate layer preparation S211. Primary mixing: Place 30 parts of modified magnesium hydroxide, 55 parts of modified calcium carbonate, 8 parts of pre-thickened styrene-acrylic emulsion, and 5 parts of talc into a high-speed kneader and stir at low speed (300 r / min) for 20 min to initially mix evenly.

[0197] S212. Secondary kneading: Heat to 60℃, stir at high speed (1000r / min) for 40min, and simultaneously introduce nitrogen (flow rate 0.3L / min) to remove air bubbles generated during the mixing process, thereby obtaining a uniform substrate slurry.

[0198] S213. Roll forming: The slurry is fed into a two-roll mill with a roll temperature of 70℃, a roll speed of 20r / min, and a rolling gap of 8mm. After three rolling passes, the thickness of the substrate layer is controlled to 8mm to ensure a dense structure (porosity of 15%-20%).

[0199] S214. Pre-curing: Place the rolled substrate layer in a constant temperature oven and pre-cur it at 80°C for 2 hours to remove some moisture and volatile components, improve the strength of the substrate layer, and avoid deformation during subsequent lamination.

[0200] S22. Preparation of microcapsule composite layer S221. Mixing and Dispersion: Place 65 parts of modified talc powder, 18 parts of microcapsule suspension (dry surface-modified microcapsules), 7 parts of aqueous styrene-acrylic emulsion, and 1 part of film-forming aid (ethylene glycol butyl ether) into a planetary mixer. First, stir at low speed (500 rpm) for 30 min, then stir at high speed (1500 rpm) for 60 min. Simultaneously, use ultrasonic-assisted dispersion (power 400W, intermittent: 10 min operation, 5 min pause, repeated 3 times) to ensure uniform dispersion of microcapsules (distribution density 50-80 particles / mm²). 2 ).

[0201] S222. Interface treatment: Coat the surface of the pre-cured substrate layer with a layer of coupling agent dilution (KH-550 and ethanol volume ratio 1:10), coating amount 5g / m². 2 After being placed at room temperature for 30 minutes, the substrate surface is activated, and the adhesion between the substrate and the microcapsule composite layer is improved (peel strength ≥ 1.5 N / mm).

[0202] S223. Slit Extrusion Coating: The microcapsule composite layer slurry is coated onto the surface of the substrate layer using a slit extrusion coating machine. The coating temperature is 50℃, the coating speed is 0.5m / min, and the coating thickness is 2mm. The thickness deviation is controlled within ±0.1mm by real-time monitoring with a laser thickness gauge.

[0203] S224. Semi-curing: The coated board is placed in a constant temperature and humidity chamber at 60℃ and 50% relative humidity for 1 hour to allow the composite layer to initially form and prevent the slurry from penetrating during subsequent surface coating.

[0204] The porosity of the microcapsule composite layer obtained above is 25%-30%.

[0205] S23 fire-resistant surface preparation S231. Preparation of surface slurry: 15 parts of intercalated modified expandable graphite, 75 parts of modified epoxy resin, 2 parts of modified nano silica, and 3 parts of coupling agent are placed in a high-speed disperser and stirred at 60°C for 60 min at a speed of 1200 r / min to form a uniform surface slurry (solid content 60%).

[0206] S232. Composite layer interface activation: Plasma treatment is performed on the surface of the semi-cured microcapsule composite layer. The plasma power is 100W, the treatment time is 3min, and the treatment distance is 5mm to improve the bonding force between the surface layer and the composite layer (peel strength ≥1.2N / mm).

[0207] S233. Doctor blade coating: The surface slurry is coated onto the surface of the microcapsule composite layer using a comma doctor blade coating machine. The coating angle is 30°, the coating speed is 0.3m / min, and the coating thickness is 2mm. After coating, the surface is smoothed a second time with a doctor blade roller to ensure the surface smoothness (surface roughness Ra≤1.0μm).

[0208] S234. Pre-drying: Place the coated board in a hot air circulating oven and pre-dry at 70°C for 2 hours to remove solvent and moisture, and avoid the formation of bubbles or pinholes during curing.

[0209] S3. Interlayer lamination and gradient curing process S31. Layer positioning: Place the pre-dried board on the hot press workbench and fix it with positioning pins to ensure that each layer is aligned (edge ​​deviation ≤ 0.5mm) to avoid misalignment between layers affecting the synergistic effect.

[0210] S32. Stepwise hot pressing curing S321. First stage (preheating and pressurization): Heat to 100℃ at a rate of 2℃ / min, apply pressure of 3MPa, and maintain the temperature and pressure for 60min to promote the initial cross-linking of each layer of adhesive and enhance the interlayer bonding.

[0211] S322. Second stage (heat curing): Continue to heat to 150℃ at a rate of 1℃ / min, increase the pressure to 6MPa, and hold at the temperature and pressure for 120min to ensure that each layer is completely cured, while ensuring that the microcapsule wall material is not damaged (the hot pressing temperature is 20-30℃ lower than the microcapsule decomposition temperature).

[0212] S323. Third stage (cooling and pressure relief): Cool down to 80℃ at a rate of 1℃ / min, reduce the pressure to 2MPa, maintain the temperature and pressure for 30min to eliminate internal stress; then cool down naturally to room temperature, release the pressure and take out the board to avoid cracking of the board due to excessive cooling.

[0213] S324. Post-curing treatment: The hot-pressed board is placed in a constant temperature oven and cured at 120°C for 4 hours to further improve the cross-linking degree of each layer and the overall mechanical properties, so that the fireproof board has a bending strength of 18MPa and a compressive strength of 25MPa.

[0214] S4. Post-processing and quality control technology S41. Cutting and finishing: The board is cut to length using a CNC cutting machine at a speed of 1m / min and a cutting accuracy of ±0.2mm. Edge burrs and irregular parts are removed to ensure that the board size meets the design requirements.

[0215] S42. Surface polishing: Polish the surface with 180-grit sandpaper at a speed of 3 m / min and a pressure of 0.1 MPa to make the surface smooth and flat, while removing residual impurities.

[0216] S43. Aging treatment: Place the sanded board in an aging test chamber at a temperature of 70℃ and a relative humidity of 90% for 72 hours.

[0217] S44. Performance testing: Conduct appearance inspection, dimensional inspection, mechanical testing, and fire extinguishing performance testing on the product.

[0218] Appearance inspection: The surface is free of cracks, bubbles, and missing materials, and the color is uniform; Dimensional inspection: thickness deviation ±0.3mm, length / width deviation ±0.5mm; Mechanical testing: flexural strength 18MPa, compressive strength 25MPa, interlaminar peel strength 1.2N / mm; Fire extinguishing performance test: After being triggered at 200℃, the gas production rate is 1.5L / (g・min) within 30 seconds, the oxygen concentration drops to below 12%, and there is no reignition after extinguishing the fire.

[0219] S45. Packaging and Storage: Qualified boards are packaged with waterproof film and pearl cotton to avoid damage during transportation; they are stored in a warehouse with a temperature of 20℃ and a relative humidity of 60%, away from fire sources and high-temperature environments, with a storage period of ≥12 months.

[0220] The fireproof board in this embodiment is used in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

[0221] A fireproof board for a new energy battery compartment is prepared from the fireproof board of this embodiment.

[0222] A fireproof partition wall panel for buildings is prepared from the fireproof panel of this embodiment. Example 3

[0223] A fireproof board comprises, from the inside out, a substrate layer, a microcapsule composite layer, and a fireproof surface layer.

[0224] The substrate layer comprises the following raw materials: 40 parts by weight of modified magnesium hydroxide, 65 parts by weight of modified calcium carbonate, 12 parts by weight of pre-thickened styrene-acrylic emulsion, and 8 parts by weight of talc.

[0225] The microcapsule composite layer comprises the following raw materials: 72 parts by weight of modified talc, 25 parts by weight of microcapsule suspension (dry surface-modified microcapsules), 10 parts by weight of water-based styrene-acrylic emulsion, and 2 parts by weight of ethylene glycol butyl ether.

[0226] The fireproof surface layer comprises the following raw materials: 20 parts by weight of intercalated modified expandable graphite, 82 parts by weight of modified epoxy resin, 4 parts by weight of modified nano silica, and 5 parts by weight of silane coupling agent KH5505.

[0227] The preparation method of microcapsules is as follows: The microcapsules in this embodiment are prepared using a four-stage process: core material pretreatment, wall material modification, stepwise encapsulation, and post-crosslinking reinforcement, as detailed below: S1. Raw material pretreatment S11. Core Material Pretreatment S111. Aminosulfonic acid (purity ≥99.5%): Processed by air jet milling with an inlet pressure of 0.8 MPa and a milling time of 30 min. The powder with a particle size of 5-10 μm was collected by passing it through a 600-mesh standard sieve and placed in a vacuum drying oven at 80℃ for 6 h to remove surface adsorbed water and prevent subsequent agglomeration.

[0228] S112. Ammonium bicarbonate (purity ≥99.0%): dried under low temperature vacuum at 50℃ and -0.09MPa for 8 hours. After crushing, it is passed through a 500-mesh sieve to control the particle size to 10-20μm to avoid premature decomposition at high temperature.

[0229] S113. Nano-montmorillonite (particle size 5-10nm): Nano-montmorillonite and hexadecyltrimethylammonium bromide are mixed at a mass ratio of 10:2, deionized water is added (solid-liquid ratio 1:30, unit is g / L), stirred at 90℃ for 3h, centrifuged (speed 4000r / min, time 20min), the precipitate is vacuum dried at 70℃ for 12h, and ground through a 500-mesh sieve to improve compatibility with organic core materials.

[0230] S12. Pretreatment of wall material raw materials S121. Ammonium polyphosphate (APP, degree of polymerization n=1500, phosphorus content 40%): APP was added to an ethanol-water mixture (ethanol to water volume ratio 7:3), solid-liquid ratio 1:25, and 5wt% (5wt% of the total mass of APP and ethanol-water mixture) of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was added. The mixture was stirred at 70℃ for 4h, and the solvent was removed by vacuum distillation (temperature 60℃, vacuum degree -0.08MPa). The mixture was then vacuum dried at 60℃ for 6h to obtain modified APP, which improves the reactivity of APP with MF resin.

[0231] S122. Preparation of melamine-formaldehyde resin (MF) prepolymer: The formaldehyde solution (mass fraction 37%) was placed in a reaction vessel at a formaldehyde to melamine molar ratio of 3.0:1. The pH was adjusted to 9.0, melamine was added, and the mixture was stirred at 50°C for 40 min until completely dissolved. The temperature was then raised to 80°C and reacted for 90 min to obtain an MF prepolymer with a solid content of 40%. The prepolymer was cooled to room temperature for later use, and the degree of hydroxymethylation was controlled to be 70%.

[0232] S2. Core Material Preparation S21. Primary mixing: Place the pretreated aminosulfonic acid and ammonium bicarbonate in a double planetary mixer at a mass ratio of 3:6, add 3wt% (3wt% of the total mass of the core material) of polyethylene glycol (PEG-6000) as a dispersant, and stir at low speed (500 r / min) for 30 min to initially mix evenly.

[0233] S22. Secondary dispersion: Add pretreated nano-montmorillonite (accounting for 20% of the total mass of the core material), heat to 80℃, stir at high speed (2000 r / min) for 60 min, and at the same time purge nitrogen (flow rate 1.0 L / min) for protection to avoid oxidative decomposition of ammonium bicarbonate.

[0234] S23. Granulation and molding: The mixed slurry is added to a spray dryer with an inlet air temperature of 180℃, an outlet air temperature of 90℃, an atomization pressure of 0.5MPa, and a feed rate of 30mL / min to obtain initial core material particles.

[0235] S24. Grading and screening: The initial core material particles after spray drying are screened by an air classifier at a grading pressure of 0.6 MPa. Core material particles with a particle size of 30-50 μm are collected, and the particle size distribution range is controlled within 1.2-1.5 to ensure the uniformity of subsequent coating.

[0236] S25. Core material stabilization treatment: The screened core material is placed in a constant temperature and humidity chamber and matured for 48 hours at a temperature of 40℃ and a relative humidity of 50% to eliminate internal stress and improve the storage stability of the core material.

[0237] S3. Wall material preparation S31. Preparation of basic emulsion: Modified APP and MF prepolymer are mixed at a mass ratio of 5:5, ethanol is added as solvent, the solid-liquid ratio is 1:12, the pH is adjusted to 8.5, and the mixture is stirred at 60℃ for 90 min at a speed of 1200 r / min to form a uniform wall material basic emulsion.

[0238] S32. Crosslinking agent adjustment: Add adipate dihydrazide equivalent to 8% of the mass of MF prepolymer as a crosslinking agent, continue stirring for 40 min, control the crosslinking degree of the wall material emulsion and the precursor content to 35%, and ensure the density of the wall material after subsequent coating.

[0239] S33. Emulsion stabilization: Add polyvinyl alcohol (PVA-1788) equivalent to 1.0 wt% of the MF prepolymer as a stabilizer, ultrasonically disperse (power 500W, time 20min) to eliminate emulsion bubbles, let stand for 30min, take the upper homogeneous emulsion for later use, and control the emulsion solid content at room temperature to 30% and the viscosity to 800mPa•s.

[0240] S4. Coating reaction S41. Pre-coating stage: Add the stabilized wall material emulsion to the reactor, introduce nitrogen gas (flow rate 1.5L / min), add the core material particles after classification and screening, with a core material particle to wall material emulsion mass ratio of 1:5, adjust pH=8.5, heat to 55℃, stir at low speed (300r / min) for 40min, and simultaneously use ultrasonic-assisted dispersion (power 300W, intermittent ultrasonic: work for 5min, pause for 3min, cycle 5 times) to make the core material particles uniformly dispersed in the wall material emulsion, forming a primary coating system.

[0241] S42. In-situ polymerization stage: The temperature is increased in stages. In the first stage, the temperature is increased to 65°C at a rate of 2°C / min, the stirring speed is increased to 700 r / min, and the reaction is carried out for 90 min to promote the initial polymerization of the wall material on the surface of the core material. In the second stage, the temperature is increased to 75°C, the stirring speed is increased to 1000 r / min, and the reaction is carried out for 120 min to form a dense three-dimensional network structure of the wall material. During the reaction, the coating thickness is sampled and tested every 30 min to control the thickness of the primary wall material to 30 μm.

[0242] S43. Post-crosslinking stage: Add melamine equivalent to 5% of the total mass of the wall material as a crosslinking agent, adjust the pH to 7.5, keep at 80℃ for 80 minutes to strengthen the crosslinking structure of the wall material and improve its thermal stability and sealing performance.

[0243] S5. Post-processing technology S51. Washing and purification: Centrifuge the encapsulated microcapsule suspension (6000 r / min, 30 min), remove the supernatant, wash 5 times with an ethanol-water mixture (volume ratio 1:1) to remove unreacted monomers and free wall material; then wash 3 times with deionized water to remove residual ethanol and ensure that there are no impurities on the surface of the microcapsules.

[0244] S52. Freeze-drying: Place the washed microcapsules in a freeze dryer, pre-freeze at -50℃ for 4 hours, then adjust the vacuum degree to 20Pa, raise the temperature to 0℃, and dry for 36 hours to avoid the core material decomposition or wall material deformation caused by high temperature, and obtain a loose and dry microcapsule intermediate.

[0245] S53. Surface-modified microcapsules: Add the microcapsule intermediate to an ethanol solution with a solid-liquid ratio of 1:15, add KH-550 silane coupling agent equivalent to 2wt% of the mass of the microcapsule intermediate, stir at 60℃ for 90 min, centrifuge (4000 r / min, 20 min), and vacuum dry at 60℃ for 6 h to improve the compatibility and bonding force between the microcapsules and the various layers of the fireproof board.

[0246] S54. Grading and Quality Control: The surface-modified microcapsules are screened by a vibrating screen with a pore size of 80-120μm to remove oversized or undersized particles and ensure uniform microcapsule size; random samples are taken to test the encapsulation rate (≥85%), wall thickness (40μm), and thermal decomposition temperature (200-230℃). Unqualified products are returned to the washing process for reprocessing.

[0247] S55. Stabilization storage: Place qualified microcapsules in a vacuum packaging container, add desiccant (montmorillonite desiccant, 8% of the mass of the microcapsules), and store at a temperature of 30℃ and a relative humidity of 50%. Shelf life is ≥12 months.

[0248] A method for preparing a fireproof board according to the present invention includes the following steps: The fireproof board of this invention adopts a five-stage preparation process: layered preparation, interface modification, stepwise composite, gradient curing, and post-treatment strengthening, as detailed below: S1. Pretreatment of raw materials for each layer of fireproof board S11. Pretreatment of substrate material S111. Magnesium hydroxide (purity ≥98%, initial particle size 10-50μm): Surface activation modification is performed by mixing magnesium hydroxide and stearic acid at a mass ratio of 100:4, adding ethanol solution (solid-liquid ratio 1:15), stirring at 80℃ for 3h, centrifuging (4000r / min, 20min), drying the precipitate under vacuum at 100℃ for 6h, grinding it through a 400-mesh sieve, controlling the particle size after modification to 10-20μm, improving compatibility and dispersion uniformity with adhesives.

[0249] S112. Calcium carbonate (heavy, whiteness ≥93%): After wet ultrafine grinding, calcium carbonate and deionized water are mixed at a mass ratio of 1:5, and sodium hexametaphosphate dispersant equivalent to 1.0 wt% of calcium carbonate is added. The grinding speed is 3000 r / min and the grinding time is 90 min. The powder is spray dried (inlet air 200℃, outlet air 90℃), and the powder with a particle size of 5-15 μm is collected and dried at 70℃ for 4 h for later use.

[0250] S113. Aqueous styrene-acrylic emulsion (solid content 50%): Pre-thickening treatment, add 0.5wt% of hydroxyethyl cellulose to the aqueous styrene-acrylic emulsion, stir at 60℃ for 40min, adjust the viscosity to 2000mPa•s (25℃) to avoid sagging during coating.

[0251] S12. Pretreatment of raw materials for microcapsule composite layers S121. Inorganic filler (talc powder, particle size 5-10μm): Silane modification is performed by mixing talc powder with KH-550 silane coupling agent at a mass ratio of 100:2, adding an ethanol-water mixed solution (the volume ratio of ethanol to water in the ethanol-water mixed solution is 6:4), with a solid-liquid ratio of 1:18, stirring at 70℃ for 3h, removing the solvent by vacuum distillation, and drying at 80℃ for 5h to improve the binding force with microcapsules and adhesives.

[0252] S122. Pretreated microcapsules: Co-dispersion treatment, surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:8, and 0.3wt% (equivalent to 0.3wt% of the total mass of microcapsules and deionized water) of polyethylene glycol (PEG-4000) is added. The mixture is then ultrasonically dispersed (power 400W, time 15min) to form a stable suspension and avoid microcapsule aggregation in the composite layer.

[0253] S13. Pretreatment of fire-resistant surface material S131. Expandable graphite (expansion ratio ≥30 times, particle size 20-50μm, model: SGL carbon, manufacturer: SGL Graphite, Germany): Mix expandable graphite and phosphoric acid at a mass ratio of 10:3, stir at 70℃ for 90 min, wash with deionized water until pH=7, centrifuge (5000 r / min, 15 min), and vacuum dry at 90℃ for 8 h to improve the expansion rate and compatibility with resin.

[0254] S132. Epoxy resin (E-44): Dilute and modify, add acetone (epoxy resin to acetone volume ratio 1:0.5), stir at 50℃ for 40 min, add 3 wt% (equivalent to 3 wt% of the total mass of epoxy resin and acetone) of triethylenetetramine curing agent, stir for 20 min, and adjust the viscosity to 1200 mPa•s (25℃).

[0255] S133. Nano silica (particle size 10-20nm): Hydrophobic modification, nano silica and methyltriethoxysilane are mixed at a mass ratio of 100:5, toluene solution is added (solid-liquid ratio 1:30), refluxed at 90℃ for 4h, filtered and dried at 100℃ for 6h to improve the surface wear resistance and self-cleaning performance.

[0256] S2. Individual preparation process for each layer S21. Substrate layer preparation S211. Primary mixing: Place 40 parts of modified magnesium hydroxide, 65 parts of modified calcium carbonate, 12 parts of pre-thickened styrene-acrylic emulsion, and 8 parts of talc into a high-speed kneader and stir at low speed (500 r / min) for 30 min to initially mix evenly.

[0257] S212. Secondary kneading: Heat to 70℃, stir at high speed (1500r / min) for 60min, and simultaneously introduce nitrogen (flow rate 0.5L / min) to remove air bubbles generated during the mixing process, and obtain a uniform substrate slurry.

[0258] S213. Roll forming: The slurry is fed into a two-roll mill with a roll temperature of 80℃, a roll speed of 30r / min, and a rolling gap of 15mm. After 5 rolling passes, the thickness of the substrate layer is controlled to 15mm to ensure a dense structure (porosity of 15%-20%).

[0259] S214. Pre-curing: Place the rolled substrate layer in a constant temperature oven and pre-cur it at 90℃ for 3 hours to remove some moisture and volatile components, improve the strength of the substrate layer, and avoid deformation during subsequent lamination.

[0260] S22. Preparation of microcapsule composite layer S221. Mixing and Dispersion: Place 72 parts of modified talc powder, 25 parts of microcapsule suspension (dry surface-modified microcapsules), 10 parts of aqueous styrene-acrylic emulsion, and 2 parts of film-forming aid (ethylene glycol butyl ether) into a planetary mixer. First, stir at low speed (800 rpm) for 40 min, then stir at high speed (2000 rpm) for 90 min. Simultaneously, use ultrasonic-assisted dispersion (500W power, intermittent: 10 min operation, 5 min pause, 4 cycles) to ensure uniform dispersion of microcapsules (distribution density 50-80 particles / mm²). 2 ).

[0261] S222. Interface treatment: Coat the surface of the pre-cured substrate layer with a layer of coupling agent dilution (KH-550 and ethanol volume ratio 1:10), coating amount 8g / m². 2 After being placed at room temperature for 60 minutes, the substrate surface is activated, and the adhesion between the substrate and the microcapsule composite layer is improved (peel strength ≥1.5N / mm).

[0262] S223. Slit Extrusion Coating: The microcapsule composite layer slurry is coated onto the surface of the substrate layer using a slit extrusion coating machine. The coating temperature is 60℃, the coating speed is 1.0m / min, and the coating thickness is 5mm. The thickness deviation is controlled within ±0.1mm by real-time monitoring with a laser thickness gauge.

[0263] S224. Semi-curing: The coated board is placed in a constant temperature and humidity chamber at 70℃ and 60% relative humidity for 2 hours to allow the composite layer to initially form and prevent the slurry from penetrating during subsequent surface coating.

[0264] The porosity of the microcapsule composite layer obtained above is 25%-30%.

[0265] S23 fire-resistant surface preparation S231. Preparation of surface slurry: 20 parts of intercalated modified expandable graphite, 82 parts of modified epoxy resin, 4 parts of modified nano silica, and 5 parts of coupling agent are placed in a high-speed disperser and stirred at 70°C for 90 min at a speed of 1800 r / min to form a uniform surface slurry (solid content 70%).

[0266] S232. Composite layer interface activation: Plasma treatment is performed on the surface of the semi-cured microcapsule composite layer. The plasma power is 150W, the treatment time is 5min, and the treatment distance is 10mm to improve the bonding force between the surface layer and the composite layer (peel strength ≥1.2N / mm).

[0267] S233. Doctor blade coating: The surface slurry is coated onto the surface of the microcapsule composite layer using a comma doctor blade coating machine. The coating angle is 45°, the coating speed is 0.8m / min, and the coating thickness is 5mm. After coating, the surface is smoothed a second time with a doctor blade roller to ensure the surface smoothness (surface roughness Ra≤1.0μm).

[0268] S234. Pre-drying: Place the coated board in a hot air circulating oven and pre-dry at 80℃ for 3 hours to remove solvent and moisture, and avoid the formation of bubbles or pinholes during curing.

[0269] S3. Interlayer lamination and gradient curing process S31. Layer positioning: Place the pre-dried board on the hot press workbench and fix it with positioning pins to ensure that each layer is aligned (edge ​​deviation ≤ 0.5mm) to avoid misalignment between layers affecting the synergistic effect.

[0270] S32. Stepwise hot pressing curing S321. First stage (preheating and pressurization): Heat to 120°C at a rate of 3°C / min, apply pressure of 5MPa, and maintain the temperature and pressure for 90min to promote the initial cross-linking of each layer of adhesive and enhance the interlayer bonding.

[0271] S322. Second stage (heating and curing): Continue to heat to 180℃ at a rate of 2℃ / min, increase the pressure to 8MPa, and hold at the temperature and pressure for 180min to ensure that each layer is completely cured, while ensuring that the microcapsule wall material is not damaged (the hot pressing temperature is 20-30℃ lower than the microcapsule decomposition temperature).

[0272] S323. Third stage (cooling and pressure relief): Cool down to 100℃ at a rate of 2℃ / min, reduce the pressure to 3MPa, maintain the temperature and pressure for 60min to eliminate internal stress; then cool down naturally to room temperature, release the pressure and take out the board to avoid cracking of the board due to excessive cooling.

[0273] S324. Post-curing treatment: The hot-pressed board is placed in a constant temperature oven and cured at 140℃ for 6 hours to further improve the cross-linking degree of each layer and the overall mechanical properties, so that the fireproof board has a bending strength of 20MPa and a compressive strength of 30MPa.

[0274] S4. Post-processing and quality control technology S41. Cutting and finishing: The board is cut to length using a CNC cutting machine at a speed of 2m / min and a cutting accuracy of ±0.2mm. Edge burrs and irregular parts are removed to ensure that the board size meets the design requirements.

[0275] S42. Surface polishing: Polish the surface with 240-grit sandpaper at a speed of 5 m / min and a pressure of 0.3 MPa to make the surface smooth and flat, while removing residual impurities.

[0276] S43. Aging treatment: Place the sanded board in an aging test chamber at a temperature of 70℃ and a relative humidity of 90% for 120 hours.

[0277] S44. Performance testing: Conduct appearance inspection, dimensional inspection, mechanical testing, and fire extinguishing performance testing on the product.

[0278] Appearance inspection: The surface is free of cracks, bubbles, and missing materials, and the color is uniform; Dimensional inspection: thickness deviation ±0.3mm, length / width deviation ±0.5mm; Mechanical testing: flexural strength 20MPa, compressive strength 30MPa, interlaminar peel strength 1.3N / mm; Fire extinguishing performance test: After being triggered at 200℃, the gas production rate is 1.8L / (g・min) within 30 seconds, the oxygen concentration drops to below 12%, and there is no reignition after extinguishing the fire.

[0279] S45. Packaging and Storage: Qualified boards are packaged with waterproof film and pearl cotton to avoid damage during transportation; they are stored in a warehouse with a temperature of 30℃ and a relative humidity of 55%, away from fire sources and high-temperature environments, with a storage period of ≥12 months.

[0280] The fireproof board in this embodiment is used in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

[0281] A fireproof board for a new energy battery compartment is prepared from the fireproof board of this embodiment.

[0282] A fireproof partition wall panel for buildings is prepared from the fireproof panel of this embodiment. Example 4

[0283] The only difference between this embodiment and Embodiment 1 is that: A fireproof board comprises, from the inside out, a substrate layer, a microcapsule composite layer, and a fireproof surface layer, wherein the substrate layer has a thickness of 12 mm, the microcapsule composite layer has a thickness of 4 mm, and the fireproof surface layer has a thickness of 4 mm.

[0284] The substrate layer comprises the following raw materials: 33 parts by weight of modified magnesium hydroxide, 62 parts by weight of modified calcium carbonate, 9 parts by weight of pre-thickened styrene-acrylic emulsion, and 7 parts by weight of talc. The microcapsule composite layer comprises the following raw materials: 68 parts by weight of inorganic filler, microcapsule suspension, 9 parts by weight of aqueous styrene-acrylic emulsion, and 2 parts by weight of film-forming aid. 22 parts by weight of surface-modified microcapsule suspension after drying; The fireproof surface layer comprises the following raw materials: 17 parts by weight of intercalated modified expandable graphite, 78 parts by weight of modified epoxy resin, 2 parts by weight of modified nano silica, and 3 parts by weight of silane coupling agent KH550.

[0285] In this invention, the method for testing the reignition rate is as follows: after extinguishing the fire, let it sit naturally for 30 minutes and observe whether it reignites.

[0286] It should be understood that, in order to simplify this disclosure and aid in understanding one or more of the various aspects of the invention, features of the invention are sometimes grouped together in a single embodiment, figure, or description thereof in the above description of exemplary embodiments of the invention. However, this method of disclosure should not be interpreted as reflecting an intention that the claimed invention requires more features than expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in fewer than all the features of the foregoingly disclosed embodiments. Therefore, the claims, following the detailed description, are hereby expressly incorporated into that detailed description, wherein each claim itself is a separate embodiment of the invention.

[0287] Although the invention has been described with reference to a limited number of embodiments, those skilled in the art will understand from the foregoing description that other embodiments are conceivable within the scope of the invention described herein. Furthermore, it should be noted that the language used in this specification has been chosen primarily for readability and edibility purposes, and not for the purpose of interpreting or limiting the subject matter of the invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the invention is illustrative and not restrictive, and the scope of the invention is defined by the appended claims.

[0288] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A fireproof board, characterized in that, From the inside out, it consists of a substrate layer, a microcapsule composite layer, and a fireproof surface layer. The substrate layer has a thickness of 8-15mm, the microcapsule composite layer has a thickness of 2-5mm, and the fireproof surface layer has a thickness of 2-5mm.

2. The fireproof board according to claim 1, characterized in that, The substrate layer comprises the following raw materials: 30-40 parts by weight of modified magnesium hydroxide, 55-65 parts by weight of modified calcium carbonate, 8-12 parts by weight of pre-thickened styrene-acrylic emulsion, and 5-8 parts by weight of talc. The microcapsule composite layer comprises the following raw materials: 65-72 parts by weight of inorganic filler, microcapsule suspension, 7-10 parts by weight of aqueous styrene-acrylic emulsion, and 1-2 parts by weight of film-forming aid. 18-25 parts by weight of surface-modified microcapsule suspension after drying; The fireproof surface layer comprises the following raw materials: 15-20 parts by weight of intercalated modified expandable graphite, 75-82 parts by weight of modified epoxy resin, 2-4 parts by weight of modified nano-silica, and 3-5 parts by weight of coupling agent.

3. A fireproof board according to claim 2, characterized in that, Inorganic fillers include modified talc; Film-forming aids include ethylene glycol butyl ether; Coupling agents include silane coupling agent KH550; The preparation method of modified magnesium hydroxide is as follows: magnesium hydroxide is surface activated and modified by mixing magnesium hydroxide and stearic acid at a mass ratio of 100:2-100:4, adding ethanol solution, solid-liquid ratio of 1:10-1:15, stirring at 70-80℃ for 2-3 hours, centrifuging separation, the precipitate is vacuum dried at 80-100℃ for 4-6 hours, and ground through a 300-400 mesh sieve. The particle size of modified magnesium hydroxide is controlled to be 10-20μm to obtain modified magnesium hydroxide. The preparation method of modified calcium carbonate is as follows: Take calcium carbonate, mix calcium carbonate and deionized water at a mass ratio of 1:3-1:5, add sodium hexametaphosphate dispersant equivalent to 0.5-1.0wt% of calcium carbonate, grind at a speed of 2000-3000 r / min for 60-90 min, spray dry, collect powder with a particle size of 5-15 μm, dry at 60-70℃ for 3-4 h for later use, and obtain modified calcium carbonate; The preparation method of pre-thickened styrene-acrylic emulsion is as follows: take an aqueous styrene-acrylic emulsion with a solid content of 40%-50%, add hydroxyethyl cellulose equivalent to 0.3-0.5 wt% of the aqueous styrene-acrylic emulsion, stir at 50-60℃ for 30-40 min, and adjust the viscosity to 1500-2000 mPa•s at 25℃ to obtain the pre-thickened styrene-acrylic emulsion; The preparation method of modified talc is as follows: talc powder and KH-550 silane coupling agent are mixed at a mass ratio of 100:1-100:2, ethanol-water mixed solution is added, the solid-liquid ratio is 1:11-1:18, the mixture is stirred at 60-70℃ for 2-3 hours, the solvent is removed by vacuum distillation, and the mixture is dried at 70-80℃ for 4-5 hours to obtain modified talc powder. The preparation method of the microcapsule suspension is as follows: surface-modified microcapsules are mixed with deionized water at a mass ratio of 1:5-1:8, and 0.2-0.3 wt% of polyethylene glycol PEG-4000 equivalent to the total mass of surface-modified microcapsules and deionized water is added. The mixture is then ultrasonically dispersed to form a stable suspension, which is the microcapsule suspension. The preparation method of intercalated modified expandable graphite is as follows: expandable graphite and phosphoric acid are mixed at a mass ratio of 10:1-10:3, stirred at 60-70℃ for 60-90 min, washed with deionized water until pH=6-7, centrifuged, and vacuum dried at 80-90℃ for 6-8 h to obtain intercalated modified expandable graphite. The preparation method of modified epoxy resin is as follows: Take epoxy resin, dilute and modify it, add acetone, the volume ratio of epoxy resin to acetone is 1:0.3-1:0.5, stir at 40-50℃ for 30-40 min, add 2-3 wt% of triethylenetetramine curing agent equivalent to the total mass of epoxy resin and acetone, stir for 15-20 min, adjust the viscosity to 800-1200 mPa•s at 25℃, and the modified epoxy resin is obtained. The modified nano silica is prepared by mixing nano silica and methyltriethoxysilane at a mass ratio of 100:3-100:5, adding toluene solution, and stirring at a solid-liquid ratio of 1:20-1:

30. After stirring under reflux at 80-90℃ for 3-4 hours, the mixture is filtered and dried at 90-100℃ for 5-6 hours to obtain the modified nano silica.

4. A fireproof board according to claim 2, characterized in that, Surface-modified microcapsules consist of a core material and a wall material; the surface of the wall material is modified with KH-550 silane coupling agent; The core material includes the following raw materials: aminosulfonic acid, ammonium bicarbonate, and modified nano-montmorillonite; The mass ratio of aminosulfonic acid to ammonium bicarbonate is 3:5-3:6, and the modified nano-montmorillonite accounts for 15%-20% of the total mass of the core material; The wall material includes the following raw materials: modified ammonium polyphosphate, melamine-formaldehyde resin prepolymer, crosslinking agent and stabilizer; the mass ratio of modified ammonium polyphosphate and melamine-formaldehyde resin prepolymer is 4:6-5:5, the weight of crosslinking agent is 5%-8% of the weight of melamine-formaldehyde resin prepolymer, and the weight of stabilizer is 0.5-1.0 wt% of the weight of melamine-formaldehyde resin prepolymer.

5. A fireproof board according to claim 4, characterized in that, Crosslinking agents include adipic acid dihydrazide; Stabilizers include polyvinyl alcohol; The preparation method of modified nano-montmorillonite is as follows: Nano-montmorillonite and hexadecyltrimethylammonium bromide are mixed at a mass ratio of 10:1-10:2, deionized water is added, the solid-liquid ratio is 1:20-1:30, the mixture is stirred at 80-90℃ for 2-3 hours, centrifuged, the precipitate is dried under vacuum at 60-70℃ for 8-12 hours, and then ground through a 300-500 mesh sieve to obtain modified nano-montmorillonite; The preparation method of modified ammonium polyphosphate is as follows: Ammonium polyphosphate is added to an ethanol-water mixed solution with a solid-liquid ratio of 1:15-1:

25. γ-glycidyl etheroxypropyltrimethoxysilane KH-560 is added at 3-5 wt% of the total mass of the ammonium polyphosphate and the ethanol-water mixed solution. The mixture is stirred at 60-70℃ for 3-4 h, the solvent is removed by vacuum distillation, and the mixture is vacuum dried at 50-60℃ for 4-6 h to obtain modified ammonium polyphosphate. The preparation method of melamine-formaldehyde resin prepolymer is as follows: Formaldehyde solution is placed in a reaction vessel at a molar ratio of formaldehyde to melamine of 2.5:1-3.0:

1. The pH is adjusted to 8.5-9.0, melamine is added, and the mixture is stirred at 40-50℃ for 30-40 minutes until completely dissolved. The temperature is then raised to 70-80℃ and reacted for 60-90 minutes to obtain a melamine-formaldehyde resin prepolymer with a solid content of 30%-40%. The prepolymer is then cooled to room temperature for later use.

6. A fireproof board according to claim 5, characterized in that, The preparation method of surface-modified microcapsules is as follows: S01. Core Material Preparation S011. Primary mixing: Place aminosulfonic acid and ammonium bicarbonate in a double planetary mixer at a mass ratio of 3:5-3:6, add 2-3wt% polyethylene glycol as a dispersant, and stir at 300-500r / min for 20-30min to achieve initial uniform mixing; S012. Secondary dispersion: Add 15%-20% of modified nano-montmorillonite by the total mass of the core material, heat to 70-80℃, stir at 1500-2000r / min for 40-60min, and simultaneously purge with nitrogen for protection. S013. Granulation and molding: The mixed slurry is added to the spray dryer to obtain the initial core material particles; S014. Grading and screening: The initial core material particles are screened by an air classifier at a grading pressure of 0.4-0.6 MPa, and core material particles with a particle size of 30-50 μm are collected, with the particle size distribution range controlled between 1.2 and 1.

5. S015. Core material stabilization treatment: Place the screened core material particles in a constant temperature and humidity chamber and mature them for 24-48 hours at a temperature of 30-40℃ and a relative humidity of 40%-50%. S02. Wall Material Preparation S021. Preparation of basic emulsion: Modified ammonium polyphosphate and melamine-formaldehyde resin prepolymer are mixed at a mass ratio of 4:6-5:5, ethanol is added as solvent, the solid-liquid ratio is 1:8-1:12, the pH is adjusted to 7.5-8.5, and the mixture is stirred at 50-60℃ for 60-90 min at a speed of 800-1200 r / min to form a uniform wall material basic emulsion; S022. Crosslinking agent adjustment: Add adipate dihydrazide at 5%-8% of the mass of melamine-formaldehyde resin prepolymer as a crosslinking agent, continue stirring for 30-40 minutes, control the crosslinking degree of the wall material emulsion and the precursor content to 25%-35%, and ensure the density of the wall material after subsequent coating. S023. Emulsion stabilization: Add polyvinyl alcohol equivalent to 0.5-1.0 wt% of the melamine-formaldehyde resin prepolymer as a stabilizer, disperse ultrasonically to eliminate emulsion bubbles, let stand for 20-30 minutes, take the upper homogeneous emulsion for later use, and control the emulsion solid content at room temperature to 25%-30% and the viscosity to 500-800 mPa•s. S03. Coating reaction S031. Pre-coating stage: Add the stabilized wall material emulsion to the reactor, introduce nitrogen gas, add the core material particles after classification and screening, with a core material particle to wall material emulsion mass ratio of 1:3-1:5, adjust the pH to 8.0-8.5, raise the temperature to 45-55℃, stir at 200-300r / min for 30-40min, and simultaneously use ultrasonic-assisted dispersion at a power of 200-300W, intermittent ultrasonication: work for 5min, pause for 3min, cycle 3-5 times, so that the core material particles are evenly dispersed in the wall material emulsion to form a primary coating system; S032. In-situ polymerization stage: The temperature is increased in stages. In the first stage, the temperature is increased to 60-65℃ at a rate of 1-2℃ / min, the stirring speed is increased to 500-700r / min, and the reaction is carried out for 60-90min to promote the initial polymerization of the wall material on the surface of the core material. In the second stage, the temperature is further increased to 70-75℃, the rotation speed is increased to 800-1000 r / min, and the reaction time is 90-120 min, so that the wall material forms a dense three-dimensional network structure; the thickness of the primary wall material is controlled at 20-30 μm. S033. Post-crosslinking stage: Add melamine equivalent to 3%-5% of the total mass of the wall material as a crosslinking agent, adjust the pH to 7.0-7.5, keep warm at 75-80℃ for 60-80 min, and obtain the coated microcapsule suspension; S04. Post-processing technology S041. Washing and purification: Centrifuge the encapsulated microcapsule suspension to remove the supernatant, wash 3-5 times with an ethanol-water mixture to remove unreacted monomers and free wall material; then wash 2-3 times with deionized water to remove residual ethanol and ensure that the surface of the microcapsules is free of impurities. S042. Freeze-drying: Place the washed microcapsules in a freeze dryer, pre-freeze at -40~-50℃ for 2-4 hours, then adjust the vacuum degree to 10-20Pa, raise the temperature to -10~0℃, and dry for 24-36 hours to obtain a loose and dry microcapsule intermediate. S043. Surface-modified microcapsules: Add the microcapsule intermediate to an ethanol solution with a solid-liquid ratio of 1:10-1:15, add 1-2 wt% of KH-550 silane coupling agent equivalent to the mass of the microcapsule intermediate, stir at 50-60℃ for 60-90 min, centrifuge, and vacuum dry at 50-60℃ for 4-6 h. S044. Grading and Quality Control: The surface-modified microcapsules are screened by a vibrating screen with a pore size of 80-120μm to obtain qualified surface-modified microcapsules with a coverage rate of ≥85%, a wall thickness of 20-40μm, and a thermal decomposition temperature of 200-230℃. S045. Stabilization storage: Place qualified surface-modified microcapsules in a vacuum packaging container, add desiccant, and store in an environment with a temperature of 20-30℃ and a relative humidity of ≤60%. Shelf life is ≥12 months.

7. A fireproof board according to claim 1, characterized in that, Flexural strength ≥18MPa, compressive strength ≥25MPa, interlaminar peel strength ≥1.2N / mm; gas generation rate ≥1.5L / (g•min) within 30s after triggering at 200℃, oxygen concentration drops to below 12%, and there is no reignition after extinguishing.

8. A method for preparing a fireproof board according to any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1. Preparation of the substrate layer S01. Primary mixing: Place 30-40 parts of modified magnesium hydroxide, 55-65 parts of modified calcium carbonate, 8-12 parts of pre-thickened styrene-acrylic emulsion, and 5-8 parts of talc into a high-speed kneader and stir at 300-500 r / min for 20-30 min until initially mixed evenly. S02. Secondary kneading: Heat to 60-70℃, stir at 1000-1500r / min for 40-60min, and simultaneously introduce nitrogen to remove air bubbles generated during the mixing process, so as to obtain a uniform substrate slurry; S03. Roll forming: The uniform substrate slurry is fed into a two-roll mill with a roll temperature of 70-80℃, a roll speed of 20-30 r / min, and a rolling gap of 8-15 mm. After 3-5 rolling passes, the substrate layer thickness is controlled to be 8-15 mm and the porosity is 15%-20% to obtain the rolled substrate layer. S04. Pre-curing: Place the rolled substrate layer in a constant temperature oven and pre-cur it at 80-90℃ for 2-3 hours to obtain the pre-cured substrate layer; Step 2. Preparation of microcapsule composite layer S05. Mixing and Dispersion: Place 65-72 parts of modified talc powder, microcapsule suspension, 7-10 parts of water-based styrene-acrylic emulsion, and 1-2 parts of film-forming aid into a planetary mixer. First, stir at 500-800 r / min for 30-40 min, then stir at 1500-2000 r / min for 60-90 min. Simultaneously, use ultrasonic-assisted dispersion at a power of 400-500 W. Intermittent operation: work for 10 min, pause for 5 min, and repeat 3-4 times to ensure uniform dispersion of microcapsules and obtain microcapsule composite layer slurry. S06. Interface Treatment: Coat the surface of the pre-cured substrate layer with a layer of coupling agent dilution (KH-550 to ethanol volume ratio 1:10), coating amount 5-8 g / m². 2 Place at room temperature for 30-60 minutes to activate the surface of the pre-cured substrate layer, improve the adhesion between the pre-cured substrate layer and the microcapsule composite layer, and achieve a peel strength ≥1.5N / mm; S07. Slit Extrusion Coating: The microcapsule composite layer slurry is coated onto the surface of the activated and pre-cured substrate layer using a slit extrusion coating machine. The coating temperature is 50-60℃, the coating speed is 0.5-1.0m / min, and the coating thickness is 2-5mm. S08. Semi-curing: The coated board is placed in a constant temperature and humidity chamber at a temperature of 60-70℃ and a relative humidity of 50%-60% for 1-2 hours to semi-cur and allow the composite layer to initially form; the porosity of the obtained microcapsule composite layer is 25%-30%; thus, the semi-cured microcapsule composite layer is obtained. Step 3. Preparation of fire-resistant surface layer S09. Preparation of surface slurry: Place 15-20 parts of intercalated modified expandable graphite, 75-82 parts of modified epoxy resin, 2-4 parts of modified nano silica, and 3-5 parts of coupling agent into a high-speed disperser, stir at 60-70℃ for 60-90 min at a speed of 1200-1800 r / min to form a uniform surface slurry with a solid content of 60%-70%. S010. Composite layer interface activation: Plasma treatment is performed on the surface of the semi-cured microcapsule composite layer. The plasma power is 100-150W, the treatment time is 3-5min, and the treatment distance is 5-10mm to improve the bonding force between the surface layer and the composite layer. The peel strength is ≥1.2N / mm. S011. Scraper coating: Apply the surface slurry to the surface of the activated semi-cured microcapsule composite layer at a coating angle of 30-45°, a coating speed of 0.3-0.8 m / min, and a coating thickness of 2-5 mm. After coating, use a scraper roller to scrape the surface smooth to ensure the surface flatness and surface roughness Ra≤1.0μm. S012. Pre-drying: The S011 coated board is placed in a hot air circulating oven and pre-dried at 70-80℃ for 2-3 hours to obtain the pre-dried board. Step 4. Interlayer lamination and gradient curing process S013. Lamination and positioning: Place the pre-dried board on the hot press workbench and fix it with positioning pins to ensure that each layer is aligned; S014. Stepwise hot pressing curing First stage: Preheating and pressurization: Heat to 100-120℃ at a rate of 2-3℃ / min, apply pressure of 3-5MPa, and maintain the temperature and pressure for 60-90min; Second stage: Heating and curing: Continue to heat up to 150-180℃ at a rate of 1-2℃ / min, increase the pressure to 6-8MPa, and hold the temperature and pressure for 120-180min; Third stage: Cooling and depressurization: Cool down to 80-100℃ at a rate of 1-2℃ / min, reduce the pressure to 2-3MPa, and maintain the temperature and pressure for 30-60min; then let it cool naturally to room temperature, depressurize and remove the board. Post-curing treatment: Place the hot-pressed board in a constant temperature oven and cure at 120-140℃ for 4-6 hours; Step 5. Post-processing and quality control: This includes cutting and trimming, surface polishing, aging treatment, performance testing, and packaging and storage.

9. The application of a fireproof board according to any one of claims 1 to 7 in fireproof boards for new energy battery compartments and fireproof boards for building partitions.

10. A fireproof board for a new energy battery compartment, characterized in that, It is prepared from the fireproof board according to any one of claims 1 to 7.